Porosity inversion and determination in gob unconsolidated materials based on acoustic signal response - Shuai-Jing Ren; Le-Xiang-Qian Zhang; Jun Deng; Jin-Rui Wang; Cai-Ping Wang; Yang Xiao; Fu-Ru Kang; Hai-Jian Li; Long-Hui Dou (Fuel, 2026)

Synergistic dual-site passivation via ionic liquid engineering for efficient and stable deep-red CsPbI₃ QLEDs - Xiaoke Li; Jinjian Lu; Rui Han; Xiaoqing Jing; Yuyu Zhang; Jintao Wang; Ren Sheng; Ping Chen (Chemical Engineering Journal, 2026)

Association of ambient PM2.5 and its components with preeclampsia risk among pregnant women in a high-altitude region - Rui Li; Zhenjuan Li; Hanping Ma; Donghua Li; Xiong Yue; Xiaoshu Zhang; Tingrong Wang; Zixuan Zou; Tianshan Shi; Xiaowei Ren (Environmental Pollution, 2026)

Smart responsive heterojunction hydrogel for synergistic therapy to promote drug-resistant diabetic wound repair and tissue regeneration - Zhiyang Ren; Rui Liu; Zhifu Liu; Xiaohan Zhang; Tianxin Wang; Lulu Chu; Wenjie Wang; Hao Wang (Chemical Engineering Journal, 2026)

Interfacial engineering of quinoa protein-guar gum complexes for 3D printable Pickering emulsions: Rheological modulation, structural fidelity, and lipophilic bioactive delivery - Rui Wang; Haizhen Mo; Zhenbin Liu; Menglin Zhang; Haipeng Ren; Lishan Yao; Shurui Peng; Xiaoling Zhu; Wei Zhou; Jiayi Zhang (Carbohydrate Polymers, 2026)

Interfacial electron redistribution stabilizes Cu-centered redox cycling for efficient Fenton-like catalysis - Xiao-Ying Li; Ruo-Lan Xu; Ren Zhu; Ting-Yu Zhang; Wen-Rui Wang; Wu-Jun Liu; Hong Jiang (Journal of Cleaner Production, 2026)

Selaginella-inspired recyclable multifunctional hydrogel sensor for wireless alert system and human-machine interaction - Qiancheng He; Lili Ren; Nan Wu; Rui Zeng; Wei Song; Mingze Han; Jingzhe Huang; Junyao Wang; Qingzhu Zhang (Chemical Engineering Journal, 2026)

Proportion-dependent asymmetric facilitation of co-invaders by arbuscular mycorrhizal fungi - Shanshan Qi; Rui Chen; Piao Lei; Zhixiang Shu; Deli Zhai; Guangqian Ren; Hongchun Wang; Xiaoling Yan; Zhicong Dai; Daolin Du; Stephen P. Bonser (Plant and Soil, 2026)

Hydrogel-encapsulated microalgae-bacteria consortia for resilient saline agriculture - Xiao-Jing Wang; Nan Wu; Xiao Yu; Si-Ming Li; Zi-Rui Yang; Zhi-Hai Zhong; Kang Wang; Hong-Li Cui; Cheng-Gang Ren; Song Qin (World Journal of Microbiology and Biotechnology, 2026)

Cascade of candidate spin liquids in a bilayer triangular-lattice antiferromagnet Rb2Co2(SeO3)3 - Xiaoyu Xu; Yunlong Wang; Xuejuan Gui; Jun Luo; Guijing Duan; Ke Shi; Zhaosheng Wang; Shuo Li; Huifen Ren; Chuanying Xi; Langsheng Ling; Zhanlong Wu; et al. (Science Bulletin, 2026)

Aeolian transport of evaporite minerals in Utopia Planitia: insights from Qaidam Basin spectral analogs - Jianxun Shen; Honglei Lin; Zhaopeng Chen; Xue Guo; Yuqi Wang; Yizhong Zhang; Li Liu; Chengxiang Huang; Enze Wang; Rui Chang; Xuesen Xu; Zhicheng Cui; et al. (Science Bulletin, 2026)

Divergent microplastic assemblages across natural and artificial waters in the Wei River Basin - Yiping Guo; Zhe Liu; Houpu Ren; Zixuan Zhang; Shichen Wei; Guojin Qi; Taishuo Zhang; Rui Wang; Xinyu Xu; Peng Liu; Hanzhong Jia (Journal of Water Process Engineering, 2026)

Preparation of P507-containing monodisperse magneto-permeable polystyrene swelling microspheres for extraction of low-concentration scandium from simulated red mud liquor - Jie Wang; Jinghan Ren; Rui Feng; Chenxi Li; Chenxin Shi; Mingqi Guo; Tianlei Yang; Yueping Guan (Journal of Water Process Engineering, 2026)

Compartment-specific host association and mobility shape ARG risk in aquaculture systems - Zhong-Quan Jiang; Rui-Kai Xing; Di Peng; Yuan-Hao Ren; Tian-Yi Wei; Wen-Bo Guo; Zhe-Min Shen; Chao-Nan Wang; Feng-Li Zhang; Tao Yuan (Journal of Hazardous Materials, 2026)

Unveiling the neurotoxic mechanism of amino-functionalized graphene quantum dots: Mitophagy-driven ferroptosis underlies progressive anxiety-like behaviors - Lifan Fan; Yutong Liu; Nanxin Ma; Rui Wang; Wenhao Wang; Qiyue Zhang; Zhihua Ren; Xia Ning; Tingting Ku (Journal of Hazardous Materials, 2026)

Development of a triplex RT-qPCR assay for rapid and accurate detection of porcine rotavirus, porcine epidemic diarrhea virus, and porcine deltacoronavirus - Yuhan Yang; Xingyu Xiao; Meixuan Ren; Ningning Jiang; Xiaoxu Xie; Xue Zheng; Rui Yin; Shiyu Luan; Jingnan Wang; Peng Li (Veterinary Research Communications, 2026)

Structure, assembly, and biological assessment of microbial communities based on eDNA metabarcoding in the continuous river-estuary-sea system of the Yellow River Estuary, China - Gang Xie; Xiaoxia Yu; Ning Zhang; Jie Li; Rui Wang; Yu Wang; Xinlei Li; Dan Li; Wanting Wang; Shilong Ren; Yi Zhu; Guoqiang Wang (Marine Pollution Bulletin, 2026)

Regulation of photosynthesis and ROS homeostasis by Fd1 and FNR1 confers thermotolerant yield stability in rice - Qiaoyan Wang; Qingmei Su; Man Li; Dongdong Chen; Yuchun Rao; Pengfei Dong; Bingxin Ye; Tingyi Wang; Zhiqi Hao; Rui Pang; Ruiying Li; Guangheng Zhang; et al. (Science Bulletin, 2026)

How to make big data accessible to plant biologists and beyond: Ten years of lessons from TBtools - Junting Feng; Chengjie Chen; Ya Wu; Longjiang Fan; Zhang Zhang; Ming Chen; Haibao Tang; Guangchuang Yu; Jian Ren; Jingchu Luo; Yi Liao; Aiping Luan; et al. (Molecular Plant, 2026)

Os79, a UDP‐Glycosyltransferase, negatively regulates cadmium tolerance and accumulation in rice - Rui Guo; Hao Yu Wang; Chong Wei Zhong; Rong Rong Ma; Jiu Huang; Jin Chen; Xian Jiao Guan; Lu Zheng; Ren Fang Shen; Ming Qing Liu; Xiao Fang Zhu (Journal of Hazardous Materials, 2026)

CO2-temperature-water nexus reshaping cherry tomato flavor: Multimodal sensing with E-nose and GC-IMS - Rui Li; Xinru Ren; Yilin Wang; Mengyan Jiang; Rongqun Wang; Zhi Zhang (Food Chemistry, 2026)

Low-dose nitrogen-doped carbon quantum dots boost medium-chain fatty acids production via enhanced proton-electron transfer - Shan-Shan Ye; Rui-Dong Xie; Yong-Yao Zhang; Qing-Lian Wu; Wei-Tong Ren; Hua-Zhe Wang; Juan-Shan Du; Wan-Qian Guo (Water Research, 2026)

Dexmedetomidine regulates fatty acid oxidation through the AMPK/PGC-1α/CPT1A pathway to mitigate renal ischaemia-reperfusion injury - Cong-Li Zhang; Yan Yan; Ke Wang; Jun-Jie Ma; Wen-Jun Xu; Gang Liu; Xing-Chun Zhu; Zhi-Gao Zhu; Hao-Feng Ding; Zi-Rui Ke; Kai Yao; Fang-Tian Fan; et al. (Toxicology and Applied Pharmacology, 2026)

Research on the fouling mechanism of nanofiltration membranes under multi-component coexistence: Synergistic effect of alkaline earth metals and fulvic acid - Xugang Song; Qiang Ma; Minglu Zhang; Rui Zhang; Hailong Wang; Xiaoxiao Duan; Yongsheng Ren (Journal of Environmental Chemical Engineering, 2026)

Zircon U-Pb dating and geochemistry of the Paleoproterozoic tuffs from the Nsama formation in northeastern Zambia - Jun-ping Ren; A-lei Gu; Hong-wei Sun; Li-bo Zuo; Jie Wang; Bao-jin Zhao; Evaristo Kasumba; Shi Xing; Zi-jiang Liu; Jin-meng Dong; Jin-rui Zhang; Ji-hai Chen (Journal of African Earth Sciences, 2026)

Study on spatiotemporal evolution characteristics of temperature field, fracture propagation and oxygen transport in coalfield fire - Fan Tao; Li-Feng Ren; Cai-Ping Wang; Ze-Yang Song; Xin Li; Jin-Rui Wang; Yi-Zhuo Jia; Jun Deng (Fuel, 2026)

Physicochemical properties, antioxidant activity, antibacterial properties, and fruit preservation potential of black soldier fly chitosan films - Bin-Qiao Yuan; Ting-Hao Yu; Jun-Kui Huang; Xin-Rui Ren; Run-Jia Wang; Guo-Xin Huang; Nortoji A. Khujamshukurov; Da-Wei Huang; Jin-Hua Xiao (Food Bioscience, 2026)

Mechanical-thermal -electrical-magnetic integration in aramid composites via binary inorganic synergy - Junchao Ren; Chenglei Huang; Rui Tan; Jianlong Chen; Mengde Huang; Shijing Song; Chengyu Yu; Hanwu Lei; Lu Wang; Bin Li; Qingfa Zhang (Chemical Engineering Journal, 2026)

CRISPR Epigenome Editing of IL1R1 Expression of Neurons that Innervate the Temporomandibular Joint or Knee Causes Reduced Sensitization to Osteoarthritic Environment - Joshua D. Stover; Robby D. Bowles; Yenisel Cruz-Almeida; Robert M. Caudle; Kyle D. Allen; Armen Akopian; Benjamin Arenkiel; Basak Ayaz; Yangjin Bae; Bruna Balbino de Paula; Anita Bandrowski; Mario Danilo Boada; et al. (Annals of Biomedical Engineering, 2026)

Renal macrostructural and hilar Doppler hemodynamic stability during a 7-day head-down tilt bed rest: an exploratory ultrasound-based study in humans under simulated microgravity - Fengxia Yu; Xia Ma; Yawen Liu; Rui Wang; Yiwen Wang; Peng-Gang Qiao; Wei Zheng; Xiangdong Hu; Linxue Qian; Pengling Ren; Zhenchang Wang (Life Sciences in Space Research, 2026)

Shading stress decreases the taste quality of rice by altering the structural and functional properties of protein - Xiaofeng Ai; Fei Deng; Qiuping Li; Yunchuan Peng; Rui Wang; Xiurong Hu; Rui Liu; Yujie Yuan; Li Wang; Hong Cheng; Youfeng Tao; Xiaolong Lei; et al. (Food Chemistry, 2026)

Triple-synergistic nanotherapeutics for acute and chronic colitis management via programmable multidimensional modulation - Penghui Wang; Yue Zhao; Ning Tian; Xiangling Liu; Tenghui Tian; Difu Zhu; Fangbing Liu; Hengyan Liu; Ling Li; Zhiyu Ren; Deok Chun Yang; Lei Zhao; et al. (Chemical Engineering Journal, 2026)

Inhibiting NAT10 suppresses hepatocellular carcinoma progression by reducing Nrf2 mRNA stability and increasing oxidative stress - Wei Gu; Ziyi Ren; Jie Gao; Ziyi Shen; Yuanhui Wang; Luanqi Xu; Rui Qian; Qinyi Miao; Yifan Wu; Xiaomeng Hu; Yan Wu; Wei Liu; et al. (Chemico-Biological Interactions, 2026)

Characterizing on-road particle number emissions from container diesel trucks using interpretable machine learning - Rui-min Hao; Hong-di He; Hong-mei Zhao; Wen-jian Jia; Zhong-ren Peng; Hui Wang (Atmospheric Pollution Research, 2026)

Overexpression of PtrPYL11 enhance drought tolerance in Populus: evidence from genome-wide identification and comparative transcriptome profiling - Shuang-Lian Deng; Shu-Ying Wei; Rui-Quan Wang; Yuan Zhang; Hao Li; Xing-Yu Liu; Xin-Ran Yu; Guan-Ru Ren; Ting Wang; Fang He (Plant Cell Reports, 2026)

Erzhi pills: a potential aging-modulating agent targeting immunosenescence in mice - Zhirui Fang; Wei Sun; Na Li; Tingting Shi; Xiuyun Ren; Rui Zhang; Yujing Zhang; Jing Chen; Qi Liu; Meng Wang; Lu Chen; Hong Wang (Biogerontology, 2026)

Dynamic hydrogen-bond-driven thorium ion traps in sodium alginate/tannic acid beads - Dingyang Chen; Chaofan Wang; Yu Yu; Zixu Ren; Rui Zhao (Journal of Hazardous Materials, 2026)

Alpaca nanobody-based sandwich ELISA for specific detection of Salmonella enteritidis in chicken - Liang Yuan; Shibo Wang; Yani Ren; Zhenghua Ji; Xinru Jiang; Beili Hao; Shuangshuang Hao; Xiaoxi Han; Changwen Li; Yicong Chang; Rui Li; Fangping Liu (Food Control, 2026)

Corrigendum to ‘Association of residential green space, blue space, and natural environment with osteoarthritis risk: The role of air pollution and phenotypic age acceleration’ [Environ. Res. volume 292 (2025) / 123632] - Jilong Bai; Panting Wei; Yao Zhang; Liying Wang; Rui Ren; Wenxu Wang; Difei Wang; Wan Yu (Environmental Research, 2026)

Association of residential green space, blue space, and natural environment with osteoarthritis risk: The role of air pollution and phenotypic age acceleration - Jilong Bai; Panting Wei; Yao Zhang; Liying Wang; Rui Ren; Wenxu Wang; Difei Wang; Wan Yu (Environmental Research, 2026)

Bioengineered functional scaffolds co-loaded with osteonectin and HA-internalizing osteoblasts for boosting bone regeneration - Wei Yang; Qin Zou; Chenxin Wang; Yuankun Ren; Rui Zhang; Mingyue Lin; Xueqi Zhang; Yu Liu; Boyang Wang; Wei Li; Li Jiang; Xiyu Li (Chemical Engineering Journal, 2026)

FeC particle electrodes derived from copper slag boost peroxymonosulfate activation for efficient antibiotic degradation: non-radical pathways mediated by 3d orbital electron reconstruction - Linjin Li; Yaoze Wang; Guangfei Qu; Rui Xu; Yingying Cai; Minhua Cheng; Nanqi Ren; Ping Lu; Minjie He; Jun Wang (Bioresource Technology, 2026)

Unraveling Successional Trajectories of Functional Microorganisms and Sulfur-Mediated Metabolic Pathways in Advanced Nitrogen Removal of Tannery Wastewater - Rui Fang; Huixue Ren; Ning Guo; Yan Jin; Weichun Liang; Chen Wei; Liya Wang; Shubing Han (Water, Air, & Soil Pollution, 2026)

The potential relationships between soil microbial communities and seed germination in the floodplain wetlands - Meng-Li Wang; Rui-Si Zhao; Xiao-Kan Wang; Jia-Ying Tian; Qian-Kun Hu; Long-Yi Yuan; You-Cai Xiong; Ai-Tian Ren (Plant and Soil, 2026)

AhNHL24 enhances peanut resistance to bacterial wilt and stem rot via glutathione and phenylpropanoid pathways - Mengtian Hou; Hao Li; Zenghui Cao; Fang Wang; Sasa Hu; Yanzhe Li; Qian Ma; Yaoyao Li; Yi Fan; Kai Zhao; Kunkun Zhao; Ding Qiu; et al. (Plant Science, 2026)

Sustainable MXene-mediated in-situ ZnO/cellulose composites via green fabrication with enhanced mechanical durability, antimicrobial activity, and EMI shielding performance - Yangyang Liu; Rui Tan; Jianlong Chen; Mengde Huang; Junchao Ren; Lu Wang; Qingfa Zhang (Journal of Cleaner Production, 2026)

Reducing grain arsenic and extracting soil arsenic in paddies by an integrated ridge–furrow and ferrihydrite–PVA membrane system - Jing-Min Yang; Qiao-Rui Ren; Zi-Xin Liu; Xin Wang; Dong-Xing Guan; Ya-Nan Dai; He Pei; Bo Peng; Qin-Bo Qin (Journal of Environmental Sciences, 2026)

Photocatalytic carbon dots for food-borne hazards: Antimicrobial and degradation mechanisms and applications in the food industry - Dangfeng Wang; Wangqing Jiang; Likun Ren; Yang Jiang; Yuqiong Meng; Rui Ma; Shulin Wang; Hongyan Guo; Fangchao Cui; Xuepeng Li; Tingting Li; Jianrong Li (Food Research International, 2026)

Ferroptosis-mediated ocular developmental toxicity of biodegradable nanoplastics in zebrafish - Yutong Liu; Lifan Fan; Nanxin Ma; Rui Wang; Qiqi Yan; Chen Chen; Wenhao Wang; Zhihua Ren; Xia Ning; Tingting Ku (Environmental Pollution, 2026)

Seawater desalination in China: Current situation, problems, and development prospects - Rui hao Wang; Cheng peng Wang; Sheng hui Wang; Dai wang Song; Pengfei Huang; Xiaoli Wang; Ren wen Ma (Desalination, 2026)

Screening of Fecal Bacteroides Strains and Discovery of Bacteroides eggerthii S13-F8 with Protective Effects Against Chemotherapy-Induced Diarrhea - Yi Zhao; Zhengqun Dai; Yanmei Lang; Rui Li; Hongyu Zheng; Jiajia Mi; Xiu He; Jin Liu; Rong Xiang; Xueran Mei; Yang Liu; Yantang Wang; et al. (Probiotics and Antimicrobial Proteins, 2026)

The transition from natural to cultivated monoculture grasslands reshapes nematode taxonomic composition without reducing diversity - Rui Yang; Xue Wei; Jinhao Ma; Xiao Ren; Yuying Wang; Bo Zhu; Pengfei Wu (Applied Soil Ecology, 2026)

Urinary metal mixtures and cataract: Findings from a U.S. population-based study and network pharmacology analysis - Runzi Yang; Jing Li; Rui Liu; Tingting Ren; Nan Wang; Liangyuan Xu; Jianmin Ma (Toxicology Letters, 2025)

Biodegradable film combined with ploughing: An approach to improve the sustainability of rainfed spring maize production - Rui Qian; Luning Du; Wenjing Li; Wei Wang; Yang Zhang; Yujie Gao; Wenjing Feng; Jiaji Ding; Wenbo Lv; Pengyao Qin; Tie Cai; Xiaolong Ren; et al. (Soil and Tillage Research, 2025)

Enhanced capacitive deionization performance of core-shell FeHCF@NiHCF Prussian blue analogue benefited from interface effect - Zewen Fan; Wannan Wang; Jing Ren; Rui-Peng Ren; Yong-Kang Lv (Journal of Environmental Chemical Engineering, 2025)

Highly efficient, selective, and sustainable adsorption of Nd3+ ion by amino-phosphonic acid functionalized polyacrylonitrile fibers via surface synergistic coordination - Xiao-Wei Zhang; Shuang Wang; Feng Guo; Jin-Xiu Wu; Yan-Hong Hu; Ming-Guang Chen; Rui-Lin Ren (Journal of Environmental Chemical Engineering, 2025)

PMTFIM: Integrating machine learning with nutrient balance theory to estimate multi-stage paddy fertilization information at field scale over large regions - Housheng Wang; Xiang Gao; Wei Jiang; Xuerong Lang; Xian Hu; Meihua Qiu; Qiankun Guo; Yonghong Liang; Xuelei Wang; Yue Mu; Rui Ren; Ganghua Li; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Facile synthesis of cationic polymer networks with ultrahigh charge density for effective capture of ReO4− (surrogate of radioactive 99TcO4−) - Minsi Shi; Dingyang Chen; Zixu Ren; Chaofan Wang; Yu Yu; Guangli Yu; Rui Zhao (Environmental Research, 2025)

Hierarchical spatiotemporal delivery system reprograms osteoclast subtypes to promote angiogenesis and bone regeneration in steroid-induced osteonecrosis of the rat femoral head - Hongyu Quan; Taiyang Li; Chencan Ren; Yuwei He; Hongkun Xie; Zibo He; Rui Wang; Haibin Ding; Jinbao Li; Shiwu Dong; Hong Jiang (Chemical Engineering Journal, 2025)

Preparation anti-fouling Janus membranes with self-cleaning capability for membrane distillation - Rui Zhang; Qiang Ma; Xugang Song; Hailong Wang; Xiaoxiao Duan; Yongsheng Ren (Chemical Engineering Journal, 2025)

Comparative analysis of sexual dimorphism in ultrastructure of sensilla on antennae, frons, and compound eyes of Azpeytia shirakii Hurkmans (Diptera: Syrphidae) - Bin Mao; Yu-Hui Cong; Ming-Hui Wang; Han-Rui Ren; Yun-Li Xiao (Zoomorphology, 2025)

DOM from eco-friendly fertilizers increases soil potential pathogen risk and shapes specific microbial populations under sprinkler and drip irrigation - Jinluo Fan; Rui Song; Heng Luo; Haijun Wu; Dongming Wu; Jun Wang; Yanqun Guo; Shuailing Hou; Mingguang Luo; Guoliang Ren; Hui Deng; Jiwei Luo; et al. (Applied Soil Ecology, 2025)

Effects of Bacillus licheniformis supplementation on growth performance, intestinal health and oxidative stress in weaning transition male dairy calves - Yulin Ma; Yubin Ma; Shuangming Yang; Yuchen Cheng; Wenyi Ren; Xiaonv Liu; Rui Wang; Yan Kang; Haibo Li; Lili Zhang; Xiaofeng Xu (Animal Feed Science and Technology, 2025)

Research on Environmental Response Characteristic of Super-Long Inclined Shaft Tunnel and CO Diffusion and Ventilation Optimization of Blasting Procedures - Kong-fei Yu; Huai-bing Wang; Hong-yan Wang; Chen-qi Fan; Bu-rui Liu; Xuan-ke Ren (Applied Geophysics, 2025)

Microplastics modulate neutrophil migration via an ROShistone lactylation positive feedback loop - Yi-li Wang; Xiao-chen Yuan; Chun-jiao Wei; Ke-yun Li; Lin-xi Zuo; Hao-yi Zhang; Rui-chen Ding; Ren Zhou; Yun-hua Zhang; Da-long Ren (Journal of Hazardous Materials, 2025)

The potential of anthraquinone-2-sulfonate (AQS) for “shell breaking” of iron-coated denitrification granular sludge - Xin-Rui Zhang; Zhi-Han Xi; Zi-Jun Yan; Xin-Tao Liu; Ying Wang; Run-Mei Li; Zi-Yue Li; Ke-Yu Wu; Ren-Cun Jin; Zai-Yong Zhang; Qian-Qian Zhang (Journal of Environmental Management, 2025)

Na/N doped carbon dot nanozymes with enhanced peroxidase activity for antimicrobial food preservation - Dangfeng Wang; Yifan Hou; Likun Ren; Yang Jiang; Yuqiong Meng; Rui Ma; Shulin Wang; Zhiteng Liu; Xuepeng Li; Fangchao Cui; Tingting Li; Jianrong Li (Food Chemistry, 2025)

Mechanism of dual-pathway peroxymonosulfate activation via Co-Nx coordination-regulated broad-pH-adaptive carbon aerogel for ciprofloxacin degradation - Linjin Li; Jun Wang; Yaoze Wang; Guangfei Qu; Rui Xu; Yingying Cai; Junyan Li; Jiao Wei; Dehui Kong; Changyi He; Minhua Cheng; Xiaofei Li; et al. (Environmental Research, 2025)

Road safety performance of a new W-beam guardrail system with rubber sandwich layer under vehicle collisions: Experimental and numerical studies - Zongwang Xie; Rui Wang; Hui Zhao; Shuo Xu; Wensu Chen; Junjun Ren (Engineering Structures, 2025)

Collaborative effects of Sr2+ and copolymer antiscalant / fulvic acid on nanofiltration membrane fouling behavior - Hailong Wang; Yunhuan Chen; Xincheng Wen; Rui Zhang; Xugang Song; Qiang Ma; Xiaoxiao Duan; Yongsheng Ren (Desalination, 2025)

Multifunctional fluorescent sensors N/CDs@Eu-MOFs for rapid detection of childhood obesity and acute myeloid leukemia biomarkers and identification of chiral enantiomers of lysine - Liping Peng; Rui Xue; Henglong Ren; Borong Ren; Mingyue Wang; Xiuli Niu; Hao Guo; Wu Yang (Analytica Chimica Acta, 2025)

Enhanced rice phosphorus use efficiency under elevated atmospheric CO2 and its drivers - Haiwei Zhang; Ting Xiao; Zihua Shi; Rui Ren; Yu Jiang; Yanfeng Ding; Songhan Wang (Agriculture, Ecosystems & Environment, 2025)

Quaternary Glaciation Accelerates Speciation in Aquatic Snakes Through Recent Bottlenecks - Jin‐Long Ren; Rui‐Han Li; Ru‐Wan Jia; Zhi‐Tong Lyu; Chaochao Yan; Dechun Jiang; Ying‐Yong Wang; Jia‐Tang Li (Molecular Ecology, 2025)
Climatic fluctuations during glacial periods have profoundly shaped the demographic history and gene flow dynamics of many taxa. This study integrated high‐throughput sequencing of 67 individuals with comprehensive genomic analyses to investigate biogeographic patterns, genetic divergence and demographic trajectories in the Opisthotropis latouchii species complex, a group of mountain stream snakes distributed across Central China. Our analyses revealed substantial genetic divergence, identifying four distinct lineages, each confined to one of the four major mountain ranges in Central China, including one previously unrecognised species. These lineages exhibited distinct demographic signatures, with population bottlenecks occurring during Quaternary glaciations. Initial isolation in the glacial refugia of the southern regions of these mountains during the Late Pliocene was followed by postglacial expansions along a northward trajectory, with further divergence along a latitudinal gradient associated with mountain distribution. Notably, the mountain ranges of Central China acted as critical refugia during glacial periods, promoting rapid speciation, and as dispersal corridors during interglacial periods, facilitating range expansion and enabling recent gene flow. These findings highlight the profound impact of Quaternary climatic oscillations on genetic structure, demographic history and gene flow patterns of these endemic taxa.

Identifying hundredfold carbon emission gaps in multiple resource recycling routes of construction waste via process and hybrid life cycle assessment - Rui Chen; Haiyuan Wu; Junjie Li; Hao Wang; Lanxin Li; Linlin Sun; Fumin Ren (Waste Management, 2025)

Inverse design of three-dimensional electrocatalytic oxidation process for water purification via machine learning and DFT-based descriptors - Linjin Li; Qiyao Wang; Yaoze Wang; Guangfei Qu; Yingying Cai; Rui Xu; Ming Jiang; Nanqi Ren (Process Safety and Environmental Protection, 2025)

Influence and mechanism of polyethylene microplastics on antibiotic resistance genes and microbial community in sludge composting process - Jie Yang; Rui Jiang; Yingchun Li; Weijian Liu; Mengmeng Wang; Peng Ren (Journal of Environmental Chemical Engineering, 2025)

Metal salt modulation strategy to prepare highly defective coal-based porous carbon for solid-state zinc ion hybrid capacitors - Pengxu Ren; Haolan Wen; Tao Wang; Yafen Zheng; Rui Sheng; Dongling Wu (Chemical Engineering Journal, 2025)

Stabilizing zinc anode with multifunctional glycine copper additive - Lang Chen; Yue Tian; Bing-Chen Liu; Bo-Xuan Zhang; Kang-Rui Ren; Zhuo-Yun Song; Pengfei Wang; Zonglin Liu; Qianyu Zhang; Jie Shu; Ting-Feng Yi (Chemical Engineering Journal, 2025)

Selective adsorptive separation of xylene isomers in vapor and liquid phases by nonporous adaptive crystals of leaning pillar[6]arenes - Yu-Xiang Sun; Susu Ren; Gengxin Wu; Xiang-Shuai Li; Haitao Wang; Jia-Rui Wu (Chemical Engineering Journal, 2025)

HMGA2 Attenuates Tendon Stem/Progenitor Cell Senescence Via PI3K/AKT-Mediated Mitophagy Activation and SASP Suppression - Hao Wang; Guang-Chun Dai; Yu-Cheng Gao; Xiao-Yu Liu; Pan-Pan Lu; Mu-Min Cao; Ren-Wang Sheng; Liu Shi; Zhang Cheng; Ying-Juan Li; Yun-Feng Rui (Stem Cell Reviews and Reports, 2025)

Jingfang granule extends lifespan and healthspan in Caenorhabditis elegans: insights from RNA-seq analysis of genetic mechanisms - Taili Zhao; Yunhua Hou; Chuanjiao Feng; Rui Zhao; Honghua Li; Peipei Zhao; Mengmeng Wang; Jingli Ren; Yiwei Meng; Kuidong Xu; Jia Liu; Xin Yin; et al. (Biogerontology, 2025)

Protective effects of rosmarinic acid against oxidative damage and atherosclerosis via the PI3K/AKT pathway - Tiantian Tang; Mingze Sun; Baiyuan Sha; Rui Liu; Zhiyang Ren; Liwei Li; Ye Zhang; Hao Wang; Kai Yu (Food and Chemical Toxicology, 2025)

PEEK-derived composite film combines high thermal conductivity and excellent joule heating properties for smart thermal management electronic sensing floors - Yageng Bai; Long Xie; Haicheng Ren; Xueling Cao; Wenchong Zhang; Fengyu Wen; Yashu He; Jierun Ma; Lin Cheng; Yifan Wang; Haoyuan Tan; Yuxuan Gu; et al. (Chemical Engineering Journal, 2025)

Monolayer graphene interlayer enhanced flexible gas sensor with fast response and high strain tolerance for wearable ammonia monitoring - Chen Wang; Ziran Wang; Feng Xu; Luyang Zhang; Haoyu Yuan; Zaiyu Zhang; Chaqi Gai; Zhongjing Ren; Haipeng Wang; Rui You; Peng Yan (Chemical Engineering Journal, 2025)

Resilience-based restoration sequence optimization of disrupted transportation networks: A novel matheuristic approach - Xinhao Cui; Bo Li; Siyue Zhang; Ziguang Ji; Shitao Wang; Rui Luo; Yi Ren; Yiyong Xiao (Transportation Research Part D: Transport and Environment, 2025)

The ultrastructure of the Cretaceous feathers highlights the evolution of the feather - Jiajia Wang; Rui Qiu; Qian Chen; Di Liu; Tongbo Zhang; Ying Li; Xinjun Zhang; Baopeng Wang; Dongyu Hu; Dong Ren; Xiaolin Wang; Xiaofei Xia; et al. (Science Bulletin, 2025)

Mn-doped copper slag with oxygen vacancies boosts peroxymonosulfate activation for ofloxacin rapid removal - Linjin Li; Yaoze Wang; Guangfei Qu; Nanqi Ren; Yanping Liu; Jiao Wei; Dehui Kong; Changyi He; Minhua Cheng; Yingying Cai; Xiaofei Li; Rui Xu (Journal of Water Process Engineering, 2025)

Coaxial emulsion electrospinning fiber films loaded with OEO for active packaging of pork - Hao Wang; Rui Ren; Mengjiao Li; Zhennan Gao; Hui Li; Simin Li (Food Research International, 2025)

Preparation of Janus membrane with self-cleaning functionality and membrane distillation performance - Rui Zhang; Yunhuan Chen; Hailong Wang; Xugang Song; Qiang Ma; Xiaoxiao Duan; Yongsheng Ren (Desalination, 2025)

Wound healing accelerated by stem cell bandage - Yingying Liu; Aman Lv; Jinjie Wu; Xiaoyan Wang; Yang Liu; Pui-In Mak; Rui P. Martins; Ren-He Xu; Yanwei Jia (Chemical Engineering Journal, 2025)

Assessment of Thermal Vulnerability and Analysis of Influencing Factors in Urban Functional Areas of Foshan City, China - Xinyue Wang; Jun Yang; Rui Zhang; Jiaxing Xin; Wenbo Yu; Jiayi Ren; Xiangming Xiao (Chinese Geographical Science, 2025)

Impact of Bacillus Licheniformis supplementation on growth performance, health status, and oxidative stress in male dairy calves during the weaning transition period - Yulin Ma; Yubin Ma; Shuangming Yang; Yuchen Cheng; Wenyi Ren; Xiaonv Liu; Rui Wang; Yan Kang; Haibo Li; Lili Zhang; Xiaofeng Xu (Animal Feed Science and Technology, 2025)

“Iron -free” CdSe/ZnS quantum dots disrupt neural differentiation of embryonic stem cells via the induction of ferroptosis - Chen Chen; Rui Wang; Yutong Liu; Lifan Fan; Nanxin Ma; Qiqi Yan; Wenhao Wang; Zhihua Ren; Xia Ning; Tingting Ku (Environmental Pollution, 2025)

Synergistic effect of canine FGF-21 combined with insulin in the treatment of canine diabetes - Wenying Sun; Yaoqun Wang; Ziran Liu; Qing Wu; Xiaochen Guo; Zhitong Li; Xinyu Li; Chunxu Shi; Rui Gao; Lin Bai; Jingming Wang; Yuhan Zhang; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Associations of ambient air pollution exposure to fine particulate matter and its chemical constituents before and during pregnancy with the risk of full-term small for gestational age: a retrospective cohort study - Tingrong Wang; Hanping Ma; Rui Li; Donghua Li; Tianshan Shi; Zhenjuan Li; Zixuan Zou; Xiaowei Ren (International Archives of Occupational and Environmental Health, 2025)

Enhancing regional-scale simulation accuracy of paddy runoff by coupling water balance models with remote sensing - Housheng Wang; Rui Ren; Xiang Gao; Huazhan Zhang; Wei Jiang; Xuerong Lang; Xian Hu; Xiaosan Jiang; Kun Zhao; Bin Zhang; Zhipeng Liu; Wenjuan Zheng; et al. (Journal of Hydrology, 2025)

Construction of linear causal-regulated and autocatalysis-driven DNA circuits for highly sensitive and specific detection of Salmonella Typhimurium - Xinru Ren; Weiqing Sun; Bowen Li; Yijing Xiao; Xudong Yue; Meili Yang; Qing-ao Pang; Rui Zhu; Zhiqiang Guo; Haiping Zhang; Yu Wang; Su Liu; et al. (Food Control, 2025)

Corrigendum to ‘Design of polypyrrole layer enhanced MIL-88B(Fe) composite electrode material for electrosorption separation of copper ions’ [Desalination 603 (15 May 2025) 118606] - Lujie Nie; Yanna Ren; Lei Wang; Yingying Wang; Jiajun An; Jiajin Hao; Jiaqi Wang; Chen Zhao; Xin Zhang; Yongtao Lv; Miaolu He; Hongyun Nie; et al. (Desalination, 2025)

Tailoring porous carbon from optimized coal blends for high-performance supercapacitor electrodes - Yanli Zhu; Tao Wang; Yan Ma; Rui Sheng; Pengxu Ren; Jia Guo; Dianzeng Jia; Dongling Wu (Chemical Engineering Journal, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Research on distributed displacement monitoring and strain inversion assessment methods for buried pipelines in fracture zones - Qunying Fan; Rui Pang; Jiajian Wang; Liang Ren; Bin Xu (Tunnelling and Underground Space Technology, 2025)

Different effects of bio/non-degradable microplastics on sewage sludge compost performance: Focusing on antibiotic resistance genes, virulence factors and key metabolic functions - Xiangyu Liu; Huiyue Li; Jie Yang; Shen Yan; Yufei Zhou; Rui Jiang; Renhe Li; Mengmeng Wang; Peng Ren (Journal of Hazardous Materials, 2025)

Association between short-term exposure to PM2.5 and its components and mumps incidence in Lanzhou, China - Zixuan Zou; Zhenjuan Li; Donghua Li; Tingrong Wang; Rui Li; Tianshan Shi; Xiaowei Ren (Environmental Pollution, 2025)

Design of polypyrrole layer enhanced MIL-88B(Fe) composite electrode material for electrosorption separation of copper ions - Lujie Nie; Yanna Ren; Lei Wang; Yingying Wang; Jiajun An; Jiajin Hao; Jiaqi Wang; Chen Zhao; Xin Zhang; Yongtao Lv; Miaolu He; Hongyun Nie; et al. (Desalination, 2025)

Recent advances and future prospects of wearable sensors based on nanomaterial sensing mechanisms for biosafety monitoring - Xiaoyu Yu; Hui Li; Junwen Wang; Xin Zhang; Rui Jiao; Yuwei Ren; Danfeng Zhang; Na Ling; Yingwang Ye (Chemical Engineering Journal, 2025)

Preparation of sodium alginate antibacterial porous composite pads embedded with centrifugally spun nanofibers by freeze-drying and recasting for active food packaging - Hao Wang; Mengjiao Li; Rui Ren; Zhennan Gao; Lingna Meng; Ziyi Li; Chuanai Cao (Carbohydrate Polymers, 2025)

Energy Release Efficiency and Mechanisms of Mining-Induced High-Energy Earthquakes in China - Zi-Bo Wang; Rui-Feng Liu; Ting-Ting Wang; Yi-Xiao Zhang; Xiao Ren (Rock Mechanics and Rock Engineering, 2025)

A template-free one-step synthesis of trimetallic nano-triangular structures significantly enhances the sensitivity of lateral flow immunoassays for acetamiprid detection - Jiahao Li; Baoshan He; Wenjie Ren; Ying Liang; Jinshui Wang; Rui Guo; Min Wei; Huali Jin (Analytica Chimica Acta, 2025)

Corrigendum to “Super antioxidant and high antibacterial ability bi-functional xylitol/2-hydroxypropyl-β-cyclodextrin carbon dots with hydroxyl-functionalized for rainbow trout preservation” [Food Research International 203 (2025) 115792] - Dangfeng Wang; Hao Dong; Yang Jiang; Likun Ren; Yuqiong Meng; Rui Ma; Shulin Wang; Zhiteng Liu; Xuepeng Li; Fangchao Cui; Tingting Li; Jianrong Li (Food Research International, 2025)

An alternative ignition agent concept based on ionic integrated energetic oxidant - Xiaoxia Li; Peng Ren; Rui Wu; Yu Wang; Peng Deng; Kehua Han; Yu Shang; Shaoli Chen; Weixiong Zhang (Chemical Engineering Journal, 2025)

In-situ surface reconstruction of BiVO4/CuFe2O4 photoanode for efficient and robust solar water oxidation - Tengfei Wang; Kai Song; Houjiang Liu; Hongyan Li; Yufei Zhang; Weijie Ren; Rui Zhang; Kun Li; Fang He; Zhenxing Qin; Huilin Hou (Chemical Engineering Journal, 2025)

Structure, sources, functional mechanisms, and applications of bioactive glycopeptides in food: A comprehensive review - Dangfeng Wang; Benyou Zhang; Likun Ren; Yang Jiang; Yuqiong Meng; Rui Ma; Shulin Wang; Xuepeng Li; Fangchao Cui; Tingting Li; Jianrong Li (Trends in Food Science & Technology, 2025)

Experimental investigation on ammonia‑nitrogen adsorption performance of ZSM-5 molecular sieve prepared from coal gangue and fly ash - Qing-Wei Li; Ye-Rui Zhu; Li-Feng Ren; Wen-Ting Xu; Yu-Xin Miao; Yang Xiao; Cai-Ping Wang (Journal of Water Process Engineering, 2025)

Molecular networking and Paterno-Büchi reaction guided glycerides characterization and antioxidant activity assessment of Ganoderma lucidum spore oil - Qing-Xuan Ren; Rui Wang; Qin-Ru Mu; Ling Chen; Min Chen; Li-Jiang Wang; Ping Li; Hua Yang; Wen Gao (Food Chemistry, 2025)

Pulsed electrolysis of Cu foil cathode assisted by reactive chlorine species for boosting low concentration nitrate wastewater denitrification - Fangyuan Liu; Zhenghong Wu; Diansheng Wang; Hejun Ren; Rui Zhou; Chunpeng Zhang (Chemical Engineering Journal, 2025)

Preparation and electrochemical properties of porous carbon derived from lignin - Zhihao Ding; Tingzhou Lei; Lili Dong; Chenghao Pan; Rui Wang; Guoli Pang; Suxia Ren (Biomass and Bioenergy, 2025)

YOLO-RCS: A method for detecting phenological period of 'Yuluxiang' pear in unstructured environment - Rui Ren; Shujuan Zhang; Haixia Sun; Ning Wang; Sheng Yang; Huamin Zhao; Mingming Xin (Computers and Electronics in Agriculture, 2025)

The role of sulfur cycle in new particle formation: Cycloaddition reaction of SO3 to H2S - Haijie Zhang; Wei Wang; Liang Fan; Junling Li; Yanqin Ren; Hong Li; Rui Gao; Yisheng Xu (Journal of Environmental Sciences, 2025)

Super antioxidant and high antibacterial ability bi-functional xylitol/2-hydroxypropyl-β-cyclodextrin carbon dots with hydroxyl-functionalized for rainbow trout preservation - Dangfeng Wang; Hao Dong; Yang Jiang; Likun Ren; Yuqiong Meng; Rui Ma; Shulin Wang; Zhiteng Liu; Xuepeng Li; Fangchao Cui; Tingting Li; Jianrong Li (Food Research International, 2025)

The characteristics of phthalate acid esters and bisphenol A in PM2.5 of a petrochemical city: Concentrations, compositions, and health risk assessment in Dongying - Fangyun Long; Yanqin Ren; Yuanyuan Ji; Xurong Bai; Hong Li; Gehui Wang; Xiaoyu Yan; Yubao Chen; Junling Li; Haijie Zhang; Rui Gao; Fang Bi; et al. (Environmental Pollution, 2025)

Revealing the combined effect of hydroxylamine and hydrazine on nitrogen removal performance of completely autotrophic nitrogen removal over nitrite (CANON) process - Xin Ma; Jia-Min Zhou; Ying-Jun Sun; Xin-Tao Liu; Xin-Rui Zhang; Ying Wang; Ying Chen; Ren-Cun Jin; Qian-Qian Zhang (Bioresource Technology, 2025)

Associations of phthalate and phthalate alternative metabolites in urine with the risk of gallstones in adults: a cross-sectional analysis - Tianshan Shi; Di Li; Donghua Li; Peng Xie; Jin Sun; Tingrong Wang; Rui Li; Zixuan Zou; Zhenjuan Li; Xiaowei Ren (Environmental Geochemistry and Health, 2025)

A new anti-inflammatory thujane monoterpenoid glycoside ester from Pittosporum heterophyllum Franch - Jia-Qi Ding; Sheng-Nan Guan; Yu-Feng Zhang; Zhao-Xuan Wang; Wei-Zhen Kong; Jun-Rui Ren; Xiu-Yun Zhang (Natural Product Research, 2025)

Smoke Simulation with Detail Enhancement in Ship Fires - Rui Tao; Hongxiang Ren; Xiao Yang; Delong Wang; Jian Sun (Journal of Marine Science and Engineering, 2025)
Smoke simulation is a crucial yet challenging aspect of constructing ship fire scenarios. For the Eulerian smoke simulation method, the low-resolution grid results in a loss of smoke detail, while the high-resolution grid faces significant computational costs. To address this issue, a detail enhancement approach is proposed for smoke simulation in ship fire scenarios based on vortex particles, aiming at high-realism smoke simulation on a low-resolution grid. The simulation domain is first discretized using a low-resolution grid to compute the basic flow. Next, the vortex particles are sampled within the grid, and the loss of vorticity is measured before and after vortex stretching to compensate for the missing smoke details. In our approach, a geometric method is employed to efficiently capture the stretching of vortex structures. The computational results demonstrate that turbulence details can be effectively captured in a low-resolution grid while maintaining the real-time performance of the simulation. The practical application value of our approach is demonstrated in improving the realism of ship fire scenarios.

Synchronous monitoring agricultural water qualities and greenhouse gas emissions based on low-cost Internet of Things and intelligent algorithms - Huazhan Zhang; Rui Ren; Xiang Gao; Housheng Wang; Wei Jiang; Xiaosan Jiang; Zhaofu Li; Jianjun Pan; Jinyang Wang; Songhan Wang; Yanfeng Ding; Yue Mu; et al. (Water Research, 2025)

Coffee, Phosphoinositide 3-Kinase Signaling Pathway, and Prostate Cancer: A Prospective Study in the Health Professionals Follow-Up Study - Rui Song; Konrad H. Stopsack; Junkun Ren; Lorelei A. Mucci; Steven K. Clinton; Massimo Loda; Molin Wang; Edward L. Giovannucci; Kathryn M. Wilson; Stephanie A. Smith-Warner (Journal of the Academy of Nutrition and Dietetics, 2025)

Construction of wheat gluten amyloid fiber/lutein complex delivery system: Formation mechanism, in vitro bioaccessibility, and photothermal stability - Tiancong Song; Ren Li; Mengmeng Zhang; Rui Kang; Huijuan Zhang; Jing Wang (Food Bioscience, 2025)

Robust and porous cationic polymeric network nanofiber membrane with high alkaline stability for efficient 99TcO4−/ReO4− removal - Minsi Shi; Dingyang Chen; Xinyue Zhao; Zixu Ren; Guangli Yu; Ce Wang; Rui Zhao; Guangshan Zhu (Chemical Engineering Journal, 2025)

Interfacial built-in electric field in 2D Ni(OH)2 heterojunction with the sodium organic compound for enhanced oxygen evolution catalysis - Jiao Zhou; Mingyuan Zhang; Baiyu Ren; Qian Yi; Hao Yu; Baoyue Zhang; Ang Li; Xinyi Hu; Zhong Li; Guanyu Chen; Yinfen Cheng; Rui Gao; et al. (Chemical Engineering Journal, 2025)

The effect of LuxR solo EvgA on the spoilage potential of Pseudomonas fluorescens - Dangfeng Wang; Benyou Zhang; Yunting Wang; Likun Ren; Yuqiong Meng; Rui Ma; Shulin Wang; Zhiteng Liu; Yang Jiang; Fangchao Cui; Tingting Li; Jianrong Li (Food Bioscience, 2024)

Corrigendum to “A critical review on graphene oxide membrane for industrial wastewater treatment” [Environ. Res. 223 (2023) 115409] - Ye-Chen An; Xiao-Xu Gao; Wen-Li Jiang; Jing-Long Han; Yuan Ye; Tian-Ming Chen; Rui-Yun Ren; Jia-Hui Zhang; Bin Liang; Zhi-Ling Li; Ai-Jie Wang; Nan-Qi Ren (Environmental Research, 2024)

Integrative experimental and computational analysis of the impact of KGM's polymerization degree on wheat starch's pasting and retrogradation characteristics - Yi Zhao; Juan Wang; Rui He; Yuanyuan Ren; Jin Fu; Yunjun Zeng; Kangyi Zhang; Geng Zhong (Carbohydrate Polymers, 2024)

On the Nearshore Significant Wave Height Inversion from Video Images Based on Deep Learning - Chao Xu; Rui Li; Wei Hu; Peng Ren; Yanchen Song; Haoqiang Tian; Zhiyong Wang; Weizhen Xu; Yuning Liu (Journal of Marine Science and Engineering, 2024)
Accurate observation of nearshore waves is crucial for coastal safety. In this study, the feasibility of extracting wave information from wave video images captured by shore-based cameras using deep learning methods was explored, focusing on inverting nearshore significant wave height (SWH) from instantaneous wave video images. The accuracy of deep learning models in classifying wind wave and swell wave images was investigated, providing reliable classification results for SWH inversion research. A classification network named ResNet-SW for wave types with improved ResNet was proposed. On this basis, the impact of instantaneous wave images, meteorological factors, and oceanographic factors on SWH inversion was evaluated, and an inversion network named Inversion-Net for SWH that integrates multiple factors was proposed. The inversion performance was significantly enhanced by the specialized models for wind wave and swell. Additionally, the inversion accuracy and stability were further enhanced by improving the loss function of Inversion-Net. Ultimately, time series inversion results were synthesized from the outputs of multiple models; the final inversion results yielded a mean absolute error of 0.04 m and a mean absolute percentage error of 8.52%. Despite certain limitations, this method can still serve as a useful alternative for wave observation.

Straw return can increase maize yield by regulating soil bacteria and improving soil properties in arid and semi-arid areas - Xiaoling Wang; Rui Qian; Yafang Han; Zhe Ji; Qingxuan Yang; Longlong Wang; Xiaoli Chen; Kun Ma; Kadambot H.M. Siddique; Zhikuan Jia; Xiaolong Ren (European Journal of Agronomy, 2024)

Nitrogen reduction enhances crop productivity, decreases soil nitrogen loss and optimize its balance in wheat-maize cropping area of the Loess Plateau, China - Jinjin Wang; Rui Qian; Jiaxiang Li; Funan Wei; Zhimeng Ma; Sisi Gao; Xu Sun; Peng Zhang; Tie Cai; Xining Zhao; Xiaoli Chen; Xiaolong Ren (European Journal of Agronomy, 2024)

A surfactant-mediated dynamic protection strategy for 100% waterborne fabrication of durable superhydrophobic coatings - Rong-Gang Zhang; Rui Feng; Fang Wang; Hang-Lin Li; Ren-Yi Sun; Hui-Hui Gao; Chun-Bo Li; Yu-Zhong Wang; Fei Song (Chemical Engineering Journal, 2024)

Multifunctional visible light photocatalytic carbon dots synergize with reactive oxygen species for anti-quorum sensing and anti-bacteria for salmon preservation - Fangchao Cui; Xin Wang; Dangfeng Wang; Likun Ren; Yuqiong Meng; Rui Ma; Shulin Wang; Zhiteng Liu; Yang Jiang; Yilin Lu; Xuepeng Li; Tingting Li; et al. (Chemical Engineering Journal, 2024)

RAD-seq data for Engelhardia roxburghiana provide insights into the palaeogeography of Hainan Island and its relationship to mainland China since the late Eocene - Pei-Han Huang; Tian-Rui Wang; Min Li; Zi-Jia Lu; Ren-Ping Su; Ou-Yan Fang; Lang Li; Shi-Shun Zhou; Yun-Hong Tan; Hong-Hu Meng; Yi-Gang Song; Jie Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Research on temperature measurement model of loose coal considering humidity using acoustic wave method - Gao-yang Qu; Jun Deng; Shuai-jing Ren; Cai-ping Wang; Ze-yang Song; Jin-rui Wang; Yu Xu; Xia-qi Zhao (Fuel, 2024)

Reason and control strategy for denitrification and anammox sludge flotation in nitrogen removal process: Mechanisms, strategies and perspectives - Xin Ma; Xin-Rui Zhang; Ying-Jun Sun; Zhi-Han Xi; Jin-Ze Liu; Ze-Tong Feng; Jia-Min Zhou; Xin-Tao Liu; Ying Wang; Ren-Cun Jin; Qian-Qian Zhang (Environmental Research, 2024)

Continuous production of pure formic acid solution from CO2 hydrogenation at room temperature via amine-functionalized PdMn nano-alloy - Xiuqin Ci; Dong Zhai; Rui Tu; Xiaoju Li; Shuchao Jiang; Xinbo Wang; Weiqiao Deng; Guoqing Ren (Chemical Engineering Journal, 2024)

Incorporating hydrogen bonding networks in microporous polymer membranes for high-flux hydrocarbon separation - Yanxiong Ren; Jingqi Fu; Rui Ding; Yunshu Li; Xu Liang; Zheyuan Guo; Jianyu Wang; Ziting Zhu; Hong Wu; Guangwei He; Zhongyi Jiang (Chemical Engineering Journal, 2024)

Investigating thermal exposure during daily walking through a human-scale approach: An analysis of a hot summer in Wuhan - Jiwei Xu; Xinkun Xu; Zimeng Wang; Huiting Chen; Qiran Ren; He Huang; Yao Cui; Rui An; Yaolin Liu (Building and Environment, 2024)

The association between the scarlet fever and meteorological factors, air pollutants and their interactions in children in northwest China - Donghua Li; Yanchen Liu; Wei Zhang; Tianshan Shi; Xiangkai Zhao; Xin Zhao; Hongmiao Zheng; Rui Li; Tingrong Wang; Xiaowei Ren (International Journal of Biometeorology, 2024)

Exposure to volatile organic compounds and growth indicators in adolescents: Unveiling the association and potential intervention strategies - Jingyi Ren; Xiaoya Sun; Zhenao Zhang; Huanting Pei; Yadong Zhang; Rui Wen; Simeng Qiao; Zidan Wang; Weican Zhang; Jinshi Zuo; Yuxia Ma (Journal of Hazardous Materials, 2024)

Adsorptive removal of aflatoxin B1 via spore protein from Aspergillus luchuensis YZ-1 - Xiyan Zhang; Rui Jiao; Yuwei Ren; Yang Wang; Hui Li; Dexin Ou; Na Ling; Yingwang Ye (Journal of Hazardous Materials, 2024)

A novel OsGST gene encoding 9glutathione reductase negatively regulates cadmium accumulation in rice - Rui Guo; Su Li; Yong Qiang Gao; Jia Tong He; Hao Yu Wang; Jin Chen; Jiu Huang; Ren Fang Shen; Xiao Fang Zhu (Journal of Hazardous Materials, 2024)

Simultaneous removal of nitrate nitrogen and ammonium nitrogen by partial denitrification coupled with anammox synergy by zero-valent iron - Jia-Min Zhou; Ying-Jun Sun; Zhi-Han Xi; Zu-Gang Liao; Xin Ma; Ze-Tong Feng; Xin-Tao Liu; Xin-Rui Zhang; Ying Wang; Ying Chen; Ren-Cun Jin; Qian-Qian Zhang (Journal of Cleaner Production, 2024)

Assessing the preservation of orbital signals across different sedimentary environments: Insights from stochastic sedimentation modeling - Meng Wang; Mingsong Li; Elizabeth A. Hajek; David B. Kemp; Yujing Wu; Hanyu Zhu; Chunju Huang; Haotian Zhang; Kaixuan Ji; Rui Zhang; Ren Wei; Zhijun Jin (Earth and Planetary Science Letters, 2024)

Molecular insights into the functional analysis of P450 CYP321A7 gene in the involvement of detoxification of lambda-cyhalothrin in Spodoptera frugiperda - Wan-Ting Li; Jia-Yu Lin; Jia-Jie Liu; Muhammad Hafeez; Shi-Wen Deng; Hong-Yu Chen; Rong-Jie Ren; Muhammad Shoaib Rana; Rui-Long Wang (Pesticide Biochemistry and Physiology, 2024)

Development of machine learning-based shelf-life prediction models for multiple marine fish species and construction of a real-time prediction platform - Fangchao Cui; Shiwei Zheng; Dangfeng Wang; Likun Ren; Yuqiong Meng; Rui Ma; Shulin Wang; Xuepeng Li; Tingting Li; Jianrong Li (Food Chemistry, 2024)

Cement-based external wall insulation material with thermal performance improvement by partial substitution of calcium silicate - Wen Rui Ren; Cheng Hai Wang; Chang Bao Han; Dong Han; Jia Yu Zheng; Ya Nan Cui; Xue Mei Song; Quan Jiang; Hui Yan (Energy and Buildings, 2024)

Comprehensive analysis of metal(loid)s and associated metal(loid) resistance genes in atmospheric particulate matter - Xiu-Peng Liang; He-Jing Wang; Jie-Ru Zheng; Xiao-Ru Wang; Dao-Ming Lin; Ya-Qing Wu; Rui-Lian Yu; Gong-Ren Hu; Yu Yan (Science of The Total Environment, 2024)

Different reference genomes determine different results: Comparing SNP calling in RAD-seq of Engelhardia roxburghiana using different reference genomes - Pei-Han Huang; Tian-Rui Wang; Min Li; Ou-Yan Fang; Ren-Ping Su; Hong-Hu Meng; Yi-Gang Song; Jie Li (Plant Science, 2024)

Bi-directional association between outdoor or social activities and cognitive function: do the PM2.5 exposure catalyze the detrimental inactivity-poor cognition cycle? - Yuling Jiang; Yifei Wu; Yang Hu; Shaojie Li; Longbin Ren; Jingjing Wang; Mingzhi Yu; Rui Yang; Zhouwei Liu; Nan Zhang; Kejia Hu; Yunquan Zhang; et al. (Environmental Research, 2024)

Super Fe3+ competing ability, high biocompatibility, and mild antibacterial carbon dots for food preservation - Fangchao Cui; Rongsen Fan; Dangfeng Wang; Likun Ren; Qianqian Wang; Yuqiong Meng; Rui Ma; Shulin Wang; Zhiteng Liu; Xuepeng Li; Tingting Li; Jianrong Li (Chemical Engineering Journal, 2024)

Individual and joint associations of per- and polyfluoroalkyl substances (PFAS) with gallstone disease in adults: A cross-sectional study - Tianshan Shi; Di Li; Donghua Li; Jin Sun; Peng Xie; Tingrong Wang; Rui Li; Zhenjuan Li; Zixuan Zou; Xiaowei Ren (Chemosphere, 2024)

Study of the fouling behavior of typical inorganic-organic foulants in silicates-bearing mine wastewater on reverse osmosis membrane - Jiapeng Li; Yunhuan Chen; Rui Zhang; Hailong Wang; Yongsheng Ren; Yulong Ma (Journal of Environmental Chemical Engineering, 2024)

Transcriptomic and biochemical analyses reveal the antifungal mechanism of cell-free supernatant from Aspergillus luchuensis YZ-1 against Aspergillus flavus - Xiyan Zhang; Rui Jiao; Yuwei Ren; Yang Wang; Hui Li; Dexin Ou; Na Ling; Yingwang Ye (Food Bioscience, 2024)

Application of a biofilm-enhanced A2O system in the treatment of wastewater from mariculture - Xiaona Ma; Rui Yin; Chen Yang; Chen Cai; Jufan Zhao; Chuxiu Lv; Xinchen Wang; Shiyu Chen; Jilong Ren; Bingzhi Zhang (Frontiers in Marine Science, 2024)
Development of environment-friendly and efficient aquaculture effluent treatment system is crucial for sustainable intensification of aquaculture, in the face of the rapidly increasing environmental pressure in the mariculture industry. In this study, mariculture wastewater was treated by the anoxic-anaerobic-oxic biochemical treatment system (A 2 O system) with traditional activated sludge replaced by nitrifying bacteria, denitrification bacteria and phosphorus accumulating bacteria absorbed on PBS carrier biofilms suitable for saline/brackish water. The results showed that biofilm-enhanced A 2 O system can effectively remove pollutants from aquaculture wastewater. The removal efficiencies of COD Mn , NH 4 + -N, TN and TP in A 2 O system were approximately 86.3%-90.8%, 97.7%-99.5%, 94.6%-95.2% and 97.0%-98.1%. The results further showed that COD Mn , NH 4 + -N, and TN were mainly removed in anaerobic tank and anoxic tank, while TP was mainly removed in the anoxic tank and oxic tank. The biofilm-enhanced A 2 O system by adding nitrifying bacteria and phosphorus accumulating bacteria biofilms using PBS as carriers instead of conventional activated sludge could be applied to the treatment of circulating aquaculture wastewater. This study provides a feasible scheme for enhancing the efficiency of A 2 O system in the treatment of aquaculture tail water, and provides a reference for the immobilization of microorganisms.

A universal mechanism on desiccation tolerance of Cronobacter based on intracellular trehalose accumulation regulated by EnvZ/OmpR - Yang Wang; Na Ling; Rui Jiao; Xiyan Zhang; Yuwei Ren; Wenhua Zhao; Hanfang Chen; Yingwang Ye (Food Microbiology, 2024)

Slope Stability Analysis under Heavy Rainfall Conditions Based on a Modified Green-Ampt Model - Yunxin Zheng; Zhiping Hu; Rui Wang; Xin Wen; Xiang Ren; Rui Pan (Water Resources Management, 2024)

Identification of abnormal closed-loop pathways in patients with MRI-negative pharmacoresistant epilepsy - Jinxin Bu; Nanxiao Ren; Yonglu Wang; Ran Wei; Rui Zhang; Haitao Zhu (Brain Imaging and Behavior, 2024)

A variable weight combination prediction model for climate in a greenhouse based on BiGRU-Attention and LightGBM - Xiaojuan Mao; Ni Ren; Peiyu Dai; Jing Jin; Baojia Wang; Rui Kang; Decui Li (Computers and Electronics in Agriculture, 2024)

Viologen-based ionic conjugated mesoporous polymer as the electron conveyer for efficient polysulfide trapping and conversion - Hai-Yang Li; Zhong-Shan Li; Gang-Hao Qiu; Rou-Rou Zhang; Ya-Rui Wang; Feng Wang; Ren-Wu Huang; Xiao-Fei Liu; Shuang-Quan Zang (Science Bulletin, 2024)

Inorganic ion accumulation model in wastewater recycling systems: Printing and dyeing case - Hanmou Dou; Xiali Jing; Wuang Ren; Rui Wang; Kai Ju; Yajiao Li; Xin Jin; Pengkang Jin (Journal of Water Process Engineering, 2024)

Cu induced reconstruction of microporous structure of tungstophosphoric acid decorated popcarbon and the synergistic effects on NH3-SCR performance - Zhaoyong Ren; Xiaoyu Qiu; Bingquan Wang; Rui Wang (Journal of Environmental Chemical Engineering, 2024)

Enhancing copper recycling through synergistic valence conversions in MnOx-modified capacitive deionization electrodes - Lujie Nie; Lei Wang; Xudong Wang; Miaolu He; Jin Wang; Yongtao Lv; Rui Miao; jiajun An; Jiajin Hao; Jiaqi Wang; Yanna Ren (Chemical Engineering Journal, 2024)

Vertical variation in magnetic particles within atmospheric PM in indoor dustfall in industrial cities of northern China - Rui Zhang; Mingrui Li; Duo Wu; Xueping Ren; Zhao Wang; Yuhan Ou (Atmospheric Pollution Research, 2024)

Resuscitation of baijiu pit mud bacteria based on Rpf protein of Umezawaea beigongshangensis - Hanxu Pan; Jiaxuan Wang; Zhanbin Sun; Rui Shi; Qing Ren (Archives of Microbiology, 2024)

Tracing spatial patterns of lacustrine groundwater discharge in a closed inland lake using stable isotopes - Xiaohui Ren; Ruihong Yu; Rui Wang; Jianfang Kang; Xiangwei Li; Pengxuan Zhang; Tingxi Liu (Journal of Environmental Management, 2024)

Optimizing maize productivity: A sustainable approach integrating straw derivatives and film mulching in rainfed agriculture - Rui Qian; Zijun Ma; Yunyun Yang; Ru Guo; Fei Han; Jinjin Wang; Xiaoling Wang; Baoping Sun; Xiaolong Ren; Xiaoli Chen; Zhikuan Jia (Field Crops Research, 2024)

Promotion of anaerobic biodegradation of azo dye RR2 by different biowaste-derived biochars: Characteristics and mechanism study by machine learning - Yu-Qian Wang; Jie Ding; Ji-Wei Pang; Chuan-Dong Wu; Han-Jun Sun; Rui Fang; Nan-Qi Ren; Shan-Shan Yang (Bioresource Technology, 2024)

Capturing spatiotemporal heterogeneity in fertilizer application for better modelling paddy water nitrogen and phosphorus pollution at regional scale - Rui Ren; Huazhan Zhang; Xiang Gao; Housheng Wang; Wei Jiang; Yuhui Wang; Xiaosan Jiang; Zhaofu Li; Haiyan Zhao; Ganghua Li; Yanfeng Ding; Yue Mu (Agriculture, Ecosystems & Environment, 2024)

Prenatal exposure to fine particulate matter chemical constituents and the risk of stillbirth and the mediating role of pregnancy complications: A cohort study - Tianshan Shi; Hanping Ma; Donghua Li; Li Pan; Tingrong Wang; Rui Li; Xiaowei Ren (Chemosphere, 2024)

Using machine learning to predict selenium and cadmium contents in rice grains from black shale-distributed farmland area - Rucan Guo; Rui Ren; Lingxiao Wang; Qian Zhi; Tao Yu; Qingye Hou; Zhongfang Yang (Science of The Total Environment, 2024)

Can straw recycling achieve sustainable agriculture at the smallholder level? A case in a semi-arid region - Rui Qian; Ru Guo; Qingxuan Yang; Muhammad Asad Naseer; Baoping Sun; Longlong Wang; Jian Zhang; Xiaolong Ren; Xiaoli Chen; Zhikuan Jia (Journal of Cleaner Production, 2024)

Regulating pathway for bacterial diversities toward improved ecological benefits of thiencarbazone-methyl·isoxaflutole application: A field experiment - Yonglu Wang; Liyun Zhang; Shumin Zhang; Shiliang Zhu; Fengsong Zhang; Guixiang Zhang; Bihua Duan; Rui Ren; Hongyu Zhang; Meng Han; Yi Xu; Yuyang Li (Journal of Environmental Management, 2024)

Estimation of water quality variables based on machine learning model and cluster analysis-based empirical model using multi-source remote sensing data in inland reservoirs, South China - Di Tian; Xinfeng Zhao; Lei Gao; Zuobing Liang; Zaizhi Yang; Pengcheng Zhang; Qirui Wu; Kun Ren; Rui Li; Chenchen Yang; Shaoheng Li; Meng Wang; et al. (Environmental Pollution, 2024)

α-Glucan derivatives as selective blockers of aldolase A: Computer-aided structure optimization and the effects on HCC - Qian-Han Xiao; Ze-Zhi Li; Li Ren; Shu-Yao Wang; Xiao-Qiang Li; Hong-Xin Bai; Rui-Zhi Qiao; Na Tang; Wen-Juan Liu; Jing-Mei Wang; Guang-Yuan Ma; Dian-Chao Dong; et al. (Carbohydrate Polymers, 2024)

In situ bioprinting of double network anti-digestive xanthan gum derived hydrogel scaffolds for the treatment of enterocutaneous fistulas - Kang Chen; Jinjian Huang; Ze Li; Jinpeng Zhang; Sicheng Li; Canwen Chen; Ye Liu; Guiwen Qu; Yitian Teng; Rui Ma; Zongan Li; Yungang Jiang; et al. (Carbohydrate Polymers, 2024)

Development and evaluation of a bivalent vaccine based on recombinant newcastle disease virus expressing infectious bursal disease virus VP2L-CH3-CH4 in SPF chickens - Wen Ying Sun; Xiao Lin Cao; Yi Xuan Wang; Xiao Chen Guo; Jin Miao Liu; Zhi Qiang Xue; Hui Juan Li; Wei Wang; Ting Ting Zhang; Qianhui Li; Rui Han Qin; Yu Han Jin; et al. (Veterinary Microbiology, 2024)

Meteoric diagenesis influenced by East Asian Summer Monsoon: A case study from the Pleistocene carbonate succession, Xisha Islands, South China Sea - Lü Wu; Rui Wang; Kefu Yu; Min Ren; Simone Booker; Ruoxia Shen; Wei Jiang; Shendong Xu; Tianlai Fan; Songye Wu; Qiushuang Qin; Xingchi Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Identification, characterization and hypolipidemic effect of novel peptides in protein hydrolysate from Protaetia brevitarsis larvae - Zong-Qi Zhang; Xin-Rui Ren; Jin Geng; Si-Cong Chen; Qing-Lei Wang; Chun-Qin Liu; Jin-Hua Xiao; Da-Wei Huang (Food Research International, 2024)

Photocatalytic degradation of benzotriazole through synergy of electron donor–acceptor units and Au clusters in covalent organic frameworks - Hui Wang; Yuhan Xiong; Yi He; Lingru Kong; Lan Ding; Rui Wu; Xin-Lei Gao; Jie Ding; Nanqi Ren (Chemical Engineering Journal, 2024)

Thymol incorporation within chitosan/polyethylene oxide nanofibers by concurrent coaxial electrospinning and in-situ crosslinking from core-out for active antibacterial packaging - Zhaozhang Zhu; Mengjia Yu; Rui Ren; Hao Wang; Baohua Kong (Carbohydrate Polymers, 2024)

High titer (>100 g/L) ethanol production from pretreated corn stover hydrolysate by modified yeast strains - Rui Zhao; Hongshen Li; Qi Li; Zefang Jia; Shizhong Li; Ling Zhao; Shan Li; Yuwei Wang; Wenxin Fan; Ruoqi Ren; Zitong Yuan; Mengchan Yang; et al. (Bioresource Technology, 2024)

Effects of dry-salting and brine-pickling on physicochemical properties and flavor of spaghetti squash shreds - Yi Luo; Rui Wang; Hui Han; Shuo Wang; Jianxiang Ma; Chunlong Yuan; Yamei Ren (Food Bioscience, 2023)

Associations of 10 trace element levels in the whole blood with risk of three types of obesity in the elderly - Rui Zhan; Lin Liu; Maoyuan Yang; Yating Ren; Zhihao Ge; Jun Shi; Ke Zhou; Jiebao Zhang; Hongjuan Cao; Linsheng Yang; Kaiyong Liu; Jie Sheng; et al. (Environmental Geochemistry and Health, 2023)

Subchronic exposure to di-(2-ethylhexyl) phthalate (DEHP) elicits blood–brain barrier dysfunction and neuroinflammation in male C57BL/6J mice - Wen-qiang Ren; Nuo Liu; Yan Shen; Xian-yan Wang; Qiong Zhou; Chen Rui; Xiao-han Yang; Sheng-long Cao; Ling-yu Li; Yán Wāng; Qu-nan Wang (Toxicology, 2023)

Integrative risk assessment method via combining geostatistical analysis, random forest, and receptor models for potentially toxic elements in selenium-rich soil - Hao Wu; Nan Cheng; Ping Chen; Fei Zhou; Yao Fan; Mingxing Qi; Jingyi Shi; Zhimin Zhang; Rui Ren; Cheng Wang; Dongli Liang (Environmental Pollution, 2023)

Mo endowment of porphyry deposits in the southern margin of the North China Craton controlled by magmatic water content - Xiaobin Miao; Rui Wang; Zengqian Hou; Yunzhen Chang; Chunhe Zhao; Yuzhong Ren (Mineralium Deposita, 2023)

Arbuscular mycorrhiza changes plant facilitation patterns and increases resource use efficiency in intercropped annual plants - Shuang-Guo Zhu; Hai-Xia Duan; Hong-Yan Tao; Li Zhu; Rui Zhou; Yu-Miao Yang; Xiao-Lin Zhang; Wen-Ying Wang; Hao Zhu; Wei Zhang; Ren-Qing Wang; Xiu-Ping Tao; et al. (Applied Soil Ecology, 2023)

Soil phosphorus availability mediates facilitation dynamic in maize-grass pea intercropping system - Shuang-Guo Zhu; Wesly Kiprotich; Zheng-Guo Cheng; Rui Zhou; Jing-Wei Fan; Hao Zhu; Wen-Ying Wang; Wei Wang; Ren-Qing Wang; Hong-Yan Tao; You-Cai Xiong (Soil and Tillage Research, 2023)

Anti-inflammatory metabolites from the fruits of Pittosporum elevaticostatum - Jun-Rui Ren; Xin-Zheng Liu; Wei-Zhen Kong; Zhao-Xuan Wang; Jin-Ming Gao; Xiu-Yun Zhang (Phytochemistry Letters, 2023)

Triazole fungicides exert neural differentiation alteration through H3K27me3 modifications: In vitro and in silico study - Tingting Ku; Xin Tan; Yutong Liu; Rui Wang; Lifan Fan; Zhihua Ren; Xia Ning; Guangke Li; Nan Sang (Journal of Hazardous Materials, 2023)

Competitive photoelectrochemical aptamer sensor based on a Z-scheme Fe2O3/g-C3N4 heterojunction for sensitive detection of lead ions - Jingui Chen; Jinxiu Zhao; Rui Feng; Hongmin Ma; Huan Wang; Xiang Ren; Qin Wei; Huangxian Ju (Journal of Hazardous Materials, 2023)

Evaluating the impact of the humic acid amendment on antibiotic resistance genes reduction and product quality during swine manure composting - Yousif Abdelrahman Yousif Abdellah; Hong-Yu Chen; Shan-Shan Sun; Xi Yang; Yu-Sen Luo; Ayodeji Bello; Taha Ahmed Mohamed; Rong-Jie Ren; Wan-Ting Li; Rashid Mohamed Ahmed; Rui-Long Wang (Journal of Environmental Chemical Engineering, 2023)

Transcriptomic analysis reveals novel desiccation tolerance mechanism of Cronobacter based on type VI secretion system inhibition - Yang Wang; Na Ling; Rui Jiao; Xiyan Zhang; Yuwei Ren; Hui Li; Wenhua Zhao; Qingping Wu; Yingwang Ye (Food Research International, 2023)

Fe/N-doped carbon dots-based nanozyme with super peroxidase activity, high biocompatibility and antibiofilm ability for food preservation - Fangchao Cui; Lanling Li; Dangfeng Wang; Likun Ren; Jiesen Li; YiLin Lu; Yuqiong Meng; Rui Ma; Shulin Wang; Xuepeng Li; Tingting Li; Jianrong Li (Chemical Engineering Journal, 2023)

Complete Genome Sequence of Streptomyces sp. HP-A2021, a Promising Bacterium for Natural Product Discovery - Lan-Fang Li; Qing-Xuan Wu; Hao Wu; Yao Li; Qian Peng; Ren-Hao Han; Da-Hu Zhang; Wei-Dong Yu; Rui Xu; Juan Wang; Zhaobin Fan; Shao-Yang Hou (Biochemical Genetics, 2023)

Megastigmane sesquiterpenoids from Saussurea medusa and their anti-inflammatory activities - Jing-Ya Cao; Qi Dong; Zhi-Yao Wang; Ye Zhao; Yu Ren; Li-Juan Mei; Yan-duo Tao; Rui-Tao Yu (Natural Product Research, 2023)

Adjusting effects of pyrolytic volatiles interaction in char to upgrade oil by swelling waste nylon-tire - Rui Huang; Qiangqiang Ren; Jialin Zhang; Limo He; Sheng Su; Yi Wang; Long Jiang; Jun Xu; Song Hu; Jun Xiang (Waste Management, 2023)

Trade-off strategy for the usage of thiencarbazone-methyl·isoxaflutole on maize fields: Nitrogen-associated microbial response and environmental implications - Yonglu Wang; Fengsong Zhang; Lida Wang; Huajun Fang; Guixiang Zhang; Xiumei Zhao; Siyi Liu; Qingchao Li; Yue Liu; Rui Ren; Yu An; Lisha Fan (Journal of Cleaner Production, 2023)

Dual-layer drug release system based on ureteral stents inhibits the formation of ureteral stricture - Zhiduan Cai; Wenjun Luo; Haoquan Zhuang; Congling Ren; Xiaolin Pan; Yuyu Xu; Haoran Wang; Xiezhao Li; Yaoji Yuan; Rui Zhu; Xiangyu Zhan; Lin Jin; et al. (Chemical Engineering Journal, 2023)

pCtFSG2, a flower-specific promoter with suitable promoter activity in safflower - Jiang Chen; Chaoxiang Ren; Jie Wang; Bin Xian; Rui Wang; Qinghua Wu; Jin Pei (Journal of Plant Biochemistry and Biotechnology, 2023)

Nickel based catalyst supported by carbon aerogel prepared from waste pomelo peel to crack ethanol for hydrogen production: Catalytic performance and mechanism - Jialin Zhang; Song Hu; Yong Ding; Rui Huang; Qiangqiang Ren; Sheng Su; Yi Wang; Long Jiang; Jun Xu; Jun Xiang (Fuel, 2023)

Insight into the structure–activity relationship in electrochromism of WO3 with rational internal cavities for broadband tunable smart windows - Xingrui Tong; Jinhui Wang; Ping Zhang; Pengyang Lei; Yi Gao; Ruirui Ren; Siyu Zhang; Rui Zhu; Guofa Cai (Chemical Engineering Journal, 2023)

Molecular insights into the dissolved organic matter of leather wastewater in leather industrial park wastewater treatment plant - Xiao-Xu Gao; Yun-Wen Wang; Ye-Chen An; Rui-Yun Ren; Yao-Hui Lin; Ning Wang; Yi-Fan Wang; Jing-Long Han; Zhi-Neng Hao; Jing-Fu Liu; Ai-Jie Wang; Nan-Qi Ren (Science of The Total Environment, 2023)

Resistant starch formation mechanism of amylosucrase-modified starches with crystalline structure enhanced by hydrothermal treatment - Ren Wang; Pinxin Rui; Tao Wang; Wei Feng; Zhengxing Chen; Xiaohu Luo; Hao Zhang (Food Chemistry, 2023)

Differential effects of petroleum-based and bio-based microplastics on anaerobic digestion: A review - Zezhou Shang; Rui Wang; Xiyi Zhang; Yongle Tu; Chenjing Sheng; Huan Yuan; Lei Wen; Yulu Li; Jing Zhang; Xiaojiao Wang; Gaihe Yang; Yongzhong Feng; et al. (Science of The Total Environment, 2023)

Short- and medium-chain chlorinated paraffins in urban road dust of Shanghai, China: concentrations, source apportionment and human exposure assessment - Xue-Tong Wang; Cheng-Lin Wang; Ying Zhou; Guo-Fa Ren; Rui Fu; Jing An (Environmental Geochemistry and Health, 2023)

A quasi-one-dimensional bulk thermoelectrics with high performance near room temperature - Qingxin Dong; Junsen Xiang; Zhen Wang; Yunxiu Li; Rui Lu; Te Zhang; Nan Chen; Yifei Huang; Yiyan Wang; Wenliang Zhu; Guodong Li; Huaizhou Zhao; et al. (Science Bulletin, 2023)

Photo-assisted thermal catalysis for methanol synthesis from methane oxidation on Cu-MOR/g-C3N4 - Yan-Qun Chen; Rui-Xin Zhang; Miao Ren; Ya-Xin Jin; Wen-Jing Wang; Jia-Yao Feng; Zhi-Hua Gao; Zhi-Feng Yan; Yi-Ming Liu; Wei Huang; Lei Liu; Zhi-Jun Zuo (Fuel, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Obliquity forcing of lake-level changes and organic carbon burial during the Late Paleozoic Ice Age - Ren Wei; Rui Zhang; Mingsong Li; Xiaojun Wang; Zhijun Jin (Global and Planetary Change, 2023)

Preparation of CeVO4/BNNS catalyst and its application in oxidation desulfurization of diesel oil - Xinyu Li; Junjun Shi; Jiangang Wang; Lei Xi; Rui Sun; Fan Zhang; Xi Wu; Zhiyong Zhou; Zhongqi Ren (Fuel, 2023)

A critical review on graphene oxide membrane for industrial wastewater treatment - Ye-Chen An; Xiao-Xu Gao; Wen-Li Jiang; Jing-Long Han; Yuan Ye; Tian-Ming Chen; Rui-Yun Ren; Jia-Hui Zhang; Bin Liang; Zhi-Ling Li; Ai-Jie Wang; Nan-Qi Ren (Environmental Research, 2023)

An ultra-thin chemical vapor deposited polymer interlayer to achieve highly improved stability of perovskite solar cell - Jing Zhou; Xueying Tian; Rui Chen; Weitao Chen; Xin Meng; Xinyu Guan; Jianan Wang; Sanwan Liu; Fumeng Ren; Shasha Zhang; Yiqiang Zhang; Zonghao Liu; et al. (Chemical Engineering Journal, 2023)

Parameter Study on How the Cervical Disc Degeneration Affects the Segmental Instantaneous Centre of Rotation - Hong Zhang; Dacheng Sang; Bin Zhang; Ya-Nan Ren; Xin Wang; Jing-Jing Feng; Cheng-Fei Du; Baoge Liu; Rui Zhu (Journal of Medical and Biological Engineering, 2023)

Quantify the effect of manure fertilizer addition and optimal nitrogen input on rainfed wheat yield and nitrogen requirement using nitrogen nutrition index - Pengzhao Liu; Xingyu Guo; Dong Zhou; Qi Zhang; Xiaolong Ren; Rui Wang; Xiaoli Wang; Xiaoli Chen; Jun Li (Agriculture, Ecosystems & Environment, 2023)

Immediate and long-term changes in the epidemiology, infection spectrum, and clinical characteristics of viral and bacterial respiratory infections in Western China after the COVID-19 outbreak: a modeling study - Tianshan Shi; Xin Zhao; Xiaoshu Zhang; Lei Meng; Donghua Li; Xinfeng Liu; Hongmiao Zheng; Deshan Yu; Tingrong Wang; Rui Li; Juansheng Li; Xiping Shen; et al. (Archives of Virology, 2023)

Diffusion simulation and risk assessment model establishment of chlorine gas leakage based on terrain conditions - Xiao-ting Ren; Xiao-ling Ma; Jiang-zheng Liu; Rui Liu; Chen-qian Zhao; Hao Wu; Zhao Wang; Chun-xu Hai; Xiao-di Zhang (Environmental Science and Pollution Research, 2023)

Heterogeneous impacts and spillover effects of green innovation network and environmental regulation on water use efficiency: A spatiotemporal perspective from 269 cities in China - Yizhen Zhang; Tao Wang; Chuantang Ren; Luwei Wang; Kun Zhang; Rui Song (Sustainable Cities and Society, 2023)

Reduced plastic film mulching under zero tillage boosts water use efficiency and soil health in semiarid rainfed maize field - Ai-Tian Ren; Ji-Yuan Li; Ling Zhao; Rui Zhou; Jian-Sheng Ye; Yi-Bo Wang; Xu-Cheng Zhang; Kiprotich Wesly; Ming-Sheng Ma; You-Cai Xiong (Resources, Conservation and Recycling, 2023)

A novel fluorescence resonance energy transfer (FRET)-based paper sensor with smartphone for quantitative detection of Vibrio parahaemolyticus - Yuwei Ren; Lulu Cao; Xiyan Zhang; Rui Jiao; Dexin Ou; Yang Wang; Danfeng Zhang; Yizhong Shen; Na Ling; Yingwang Ye (Food Control, 2023)

Exploring the heterogeneity in drivers of energy-saving behaviours among hotel guests: Insights from the theory of planned behaviour and personality profiles - Qian-Cheng Wang; Yi-Tian Ren; Xuan Liu; Rui-Dong Chang; Jian Zuo (Environmental Impact Assessment Review, 2023)

High density mapping of wheat stripe rust resistance gene QYrXN3517-1BL using QTL mapping, BSE-Seq and candidate gene analysis - Shuo Huang; Yibo Zhang; Hui Ren; Xin Zhang; Rui Yu; Shengjie Liu; Qingdong Zeng; Qilin Wang; Fengping Yuan; Ravi P. Singh; Sridhar Bhavani; Jianhui Wu; et al. (Theoretical and Applied Genetics, 2023)

Association of Glial Activation and α-Synuclein Pathology in Parkinson’s Disease - Rui Wang; Haigang Ren; Elena Kaznacheyeva; Xiaojun Lu; Guanghui Wang (Neuroscience Bulletin, 2023)
The accumulation of pathological α-synuclein (α-syn) in the central nervous system and the progressive loss of dopaminergic neurons in the substantia nigra pars compacta are the neuropathological features of Parkinson's disease (PD). Recently, the findings of prion-like transmission of α-syn pathology have expanded our understanding of the region-specific distribution of α-syn in PD patients. Accumulating evidence suggests that α-syn aggregates are released from neurons and endocytosed by glial cells, which contributes to the clearance of α-syn. However, the activation of glial cells by α-syn species produces pro-inflammatory factors that decrease the uptake of α-syn aggregates by glial cells and promote the transmission of α-syn between neurons, which promotes the spread of α-syn pathology. In this article, we provide an overview of current knowledge on the role of glia and α-syn pathology in PD pathogenesis, highlighting the relationships between glial responses and the spread of α-syn pathology.

One-dimensional copper bromide based inorganic-organic hybrids as fuels for hypergolic bipropellants with hydrogen peroxide as oxidizer - Ya-Jie Wang; Xu-Yang Wang; Hong Xu; Wei-Wei Ren; Rui Pang; Li Yang; Wen-Chao Tong; Qian-You Wang; Shuang-Quan Zang (Chemical Engineering Journal, 2023)

Construction of 3D Ni2+-Al3+-LDH/γ-Fe2O3-Cd2+-Ni2+-Fe3+-LDH structures and multistage recycling treatment of dye and fluoride-containing wastewater - Rui Dang; Xiang-Rong Ma; Yun-Peng Zhao; Menjiao Ren; Wei Guo; Yu-Hong Kang; Yong Gao; Shiqing Bi; Wenwen Gao; Hua-Rui Hao; Rui Bai; Yu-Fei Wang; et al. (Chemical Engineering Journal, 2023)

Selenite Ameliorates Cadmium-induced Cytotoxicity Through Downregulation of ROS Levels and Upregulation of Selenoprotein Thioredoxin Reductase 1 in SH-SY5Y Cells - Hecheng Wang; Shibo Sun; Yan Ren; Rui Yang; Jianli Guo; Yu Zong; Qiuxian Zhang; Jing Zhao; Wei Zhang; Weiping Xu; Shui Guan; Jianqiang Xu (Biological Trace Element Research, 2023)

Evaluating the effects of contact time and leaching solution on measured solubilities of aerosol trace metals - Rui Li; Shuwei Dong; Chengpeng Huang; Feng Yu; Fu Wang; Xiaofei Li; Huanhuan Zhang; Yan Ren; Mingxian Guo; Qingcai Chen; Baozhu Ge; Mingjin Tang (Applied Geochemistry, 2023)

Development of a matrix-based candidate reference material for human glycated albumin using isotope-dilution liquid chromatography/tandem mass spectrometry - Rui Zhang; Rui Zhao; Wenhua Ren; Mo Wang; Gaowei Fan; Jie Shi; Yichuan Song; Xiaojie Zhou; Qingtao Wang (Analytica Chimica Acta, 2023)

Modification of TiO2 by Er3+ and rGO enhancing visible photocatalytic degradation of arsanilic acid - Xinghao Ren; Hang Yao; Rui Tang; Rong A; Shoujun Yuan; Wei Wang; Ibrahim Mohamed Ali; Zhen-Hu Hu (Environmental Science and Pollution Research, 2022)

MCPIP1 alleviated alcohol-induced immune dysfunction via the MAPK/ERK signaling pathway - Yanjie Shen; Kai Zhang; Rui Wang; Shuaichen Sun; Yating Yang; Yitan Yao; Huanzhong Liu; Zhenhua Ren (Psychopharmacology, 2022)

The protective effects of procyanidin supplementation on PM2.5-induced acute cardiac injury in rats - Bowen Yin; Xiao Zhang; Jingyi Ren; Fengge Chen; Jufeng Liang; Hanning Zhang; Huanting Pei; Zhaohui Hu; Yan Wang; Wei Xue; Xinyue Yu; Rui Zhang; et al. (Environmental Science and Pollution Research, 2022)

Magnetic Resonance Imaging Markers of Cerebral Small Vessel Disease in Adults with Moyamoya Disease - Haogeng Sun; Wanjiang Li; Chao Xia; Yutao Ren; Lu Ma; Anqi Xiao; Chao You; Xiaoyu Wang; Rui Tian; Yi Liu (Translational Stroke Research, 2022)

The interplay of particle properties and solution chemistry on aggregation kinetics of soil nanoparticles - Ning Hu; Chen-yang Xu; Zeng-chao Geng; Fei-nan Hu; Qi-rui Li; Ren-tian Ma; Qiang Wang (Journal of Soils and Sediments, 2022)

Early changes to the extracellular space in the hippocampus under simulated microgravity conditions - Yajuan Gao; Hongbin Han; Jichen Du; Qingyuan He; Yanxing Jia; Junhao Yan; Hui Dai; Bin Cui; Jing Yang; Xunbin Wei; Liu Yang; Rui Wang; et al. (Science China Life Sciences, 2022)

Identification of epigenetic modifications mediating the antagonistic effect of selenium against cadmium-induced breast carcinogenesis - Zhuo-Zhi Liang; Yi-Xin Zhang; Rui-Mei Zhu; Yue-Lin Li; Hong-Mei Jiang; Ruo-Bi Li; Qian-Xin Chen; Qing Wang; Lu-Ying Tang; Ze-Fang Ren (Environmental Science and Pollution Research, 2022)

Hierarchical porous polystyrene-based activated carbon spheres for CO2 capture - Xiaoxia Ren; Changming Zhang; Lifang Kou; Rongxian Wang; Yaqi Wang; Rui Li (Environmental Science and Pollution Research, 2022)

Co-composting of fresh tobacco leaves and soil: an exploration on the utilization of fresh tobacco waste in farmland - Huihui Di; Rui Wang; Xiaohong Ren; Jianqiang Deng; Xiaohua Deng; Guijun Bu (Environmental Science and Pollution Research, 2022)

ROS-induced oxidative stress in plant cryopreservation: occurrence and alleviation - Li Ren; Min-Rui Wang; Qiao-Chun Wang (Planta, 2021)
Main conclusion Reactive oxygen species (ROS)-induced oxidative stress results in low success or even total failure of cryopreservation. Better understanding of how the plant establishes resistance/tolerance to ROS-induced oxidative stress facilitates developments of robust cryopreservation procedures. Abstract Cryopreservation provides a safe and efficient strategy for long-term preservation of plant genetic resources. ROS-induced oxidative stress caused damage to cells and reduced the ability of the plant to survive following cryopreservation, eventually resulting in low success or even total failure. This paper provides updated and comprehensive information obtained in the past decade, including the following: (1) ROS generations and adaptive responses of antioxidant systems during cryopreservation; (2) expressions of oxidative stress-associated genes and proteins during cryopreservation; (3) ROS-triggered programmed cell death (PCD) during cryopreservation; and (4) exogenous applications of enzymatic and non-enzymatic antioxidants in improving success of cryopreservation. Prospects for further studies are proposed. The goal of the present study was to facilitate better understanding of the mechanisms by which the plant establishes resistance/tolerance to oxidative stress during cryopreservation and promote further studies toward the developments of robust cryopreservation procedures and wider application of plant cryobiotechnology.

Sigma-1 Receptor Activation Suppresses Microglia M1 Polarization via Regulating Endoplasmic Reticulum–Mitochondria Contact and Mitochondrial Functions in Stress-Induced Hypertension Rats - Kokwin Ooi; Li Hu; Yi Feng; Chenzhi Han; Xiaorong Ren; Xinyi Qian; Haofeng Huang; Sijia Chen; Qi Shi; Hong Lin; Jijiang Wang; Danian Zhu; et al. (Molecular Neurobiology, 2021)

Gisenoside Rg1 attenuates cadmium-induced neurotoxicity in vitro and in vivo by attenuating oxidative stress and inflammation - Teng-Teng Ren; Jia-Ying Yang; Jun Wang; Sheng-Rui Fan; Rongfeng Lan; Xiao-Yan Qin (Inflammation Research, 2021)

Occurrence, source apportionment, and carcinogenic risk assessment of polycyclic aromatic hydrocarbons in urban road dusts in Shanghai - Xue-Tong Wang; Rui Fu; Ying Zhou; Cheng-Lin Wang; Guo-Fa Ren; Xiao-Li Wang; Hui Li (Environmental Science and Pollution Research, 2021)

Detoxification difference of cadmium between the application of selenate and selenite in native cadmium-contaminated soil - Mingxing Qi; Yang Liu; Yanan Li; Min Wang; Nana Liu; Pornpimol Kleawsampanjai; Fei Zhou; Hui Zhai; Mengke Wang; Quang Toan Dinh; Rui Ren; Dongli Liang (Environmental Science and Pollution Research, 2021)

Triculata A, a novel compound from Tricyrtis maculata (D. Don) J. F. Macbr. with biological properties - Li Ren; Yun-Ze Wang; Wei Zhang; Rui Zhou; Ming Zhao; Zhi-Shu Tang; Jing Sun; Dong-Bo Zhang (Natural Product Research, 2021)

Ecological risk assessment of heavy metals in farmland soils in Beijing by three improved risk assessment methods - Rui Chen; Xuying Cai; Guoyu Ding; Fumin Ren; Qi Wang; Nuo Cheng; Jiaxing Liu; Lanxin Li; Rongguang Shi (Environmental Science and Pollution Research, 2021)

Chronic Exposure to Hypoxia Inhibits Myelinogenesis and Causes Motor Coordination Deficits in Adult Mice - Lin Chen; Shu-Yu Ren; Rui-Xue Li; Kun Liu; Jing-Fei Chen; Yu-Jian Yang; Yong-Bin Deng; Han-Zhi Wang; Lan Xiao; Feng Mei; Fei Wang (Neuroscience Bulletin, 2021)
Exposure to chronic hypoxia is considered to be a risk factor for deficits in brain function in adults, but the underlying mechanisms remain largely unknown. Since active myelinogenesis persists in the adult central nervous system, here we aimed to investigate the impact of chronic hypoxia on myelination and the related functional consequences in adult mice. Using a transgenic approach to label newly-generated myelin sheaths ( NG2-CreER TM ; Tau-mGFP ), we found that myelinogenesis was highly active in most brain regions, such as the motor cortex and corpus callosum. After exposure to hypoxia (10% oxygen) 12 h per day for 4 weeks, myelinogenesis was largely inhibited in the 4-month old brain and the mice displayed motor coordination deficits revealed by the beam-walking test. To determine the relationship between the inhibited myelination and functional impairment, we induced oligodendroglia-specific deletion of the transcription factor Olig2 by tamoxifen ( NG2-CreER TM ; Tau-mGFP; Olig2 fl/fl ) in adult mice to mimic the decreased myelinogenesis caused by hypoxia. The deletion of Olig2 inhibited myelinogenesis and consequently impaired motor coordination, suggesting that myelinogenesis is required for motor function in adult mice. To understand whether enhancing myelination could protect brain functions against hypoxia, we treated hypoxic mice with the myelination-enhancing drug-clemastine, which resulted in enhanced myelogenesis and improved motor coordination. Taken together, our data indicate that chronic hypoxia inhibits myelinogenesis and causes functional deficits in the brain and that enhancing myelinogenesis protects brain functions against hypoxia-related deficits.

Dicer Deletion in Astrocytes Inhibits Oligodendroglial Differentiation and Myelination - Kun Liu; Bin Yu; Jing-Fei Chen; Rui-Xue Li; Lin Chen; Shu-Yu Ren; Fei Wang; Feng Mei; Lan Xiao (Neuroscience Bulletin, 2021)
Increasing evidence has shown that astrocytes are implicated in regulating oligodendrocyte myelination, but the underlying mechanisms remain largely unknown. To understand whether microRNAs in astrocytes function in regulating oligodendroglial differentiation and myelination in the developing and adult CNS, we generated inducible astrocyte-specific Dicer conditional knockout mice (hGFAP-CreERT; Dicer fl/fl). By using a reporter mouse line (mT/mG), we confirmed that hGFAP-CreERT drives an efficient and astrocyte-specific recombination in the developing CNS, upon tamoxifen treatment from postnatal day 3 (P3) to P7. The Dicer deletion in astrocytes resulted in inhibited oligodendroglial differentiation and myelination in the developing CNS of Dicer cKO mice at P10 and P14, and did not alter the densities of neurons or axons, indicating that Dicer in astrocytes is required for oligodendrocyte myelination. Consequently, the Dicer deletion in astrocytes at P3 resulted in impaired spatial memory and motor coordination at the age of 9 weeks. To understand whether Dicer in astrocytes is also required for remyelination, we induced Dicer deletion in 3-month-old mice and then injected lysolecithin into the corpus callosum to induce demyelination. The Dicer deletion in astrocytes blocked remyelination in the corpus callosum 14 days after induced demyelination. Together, our results indicate that Dicer in astrocytes is required for oligodendroglia myelination in both the developing and adult CNS.

Spatial Heterogeneity of Agricultural Science and Technology Parks Technology Diffusion: A Case Study of Yangling ASTP - Zhao Wang; Jianhong Liu; Tongsheng Li; Wanying Ren; Yang Rui (Chinese Geographical Science, 2021)

Swi6B , an alternative splicing isoform of Swi6, mediates the cell wall integrity of Ganoderma lucidum - Lingdan Lian; Guang Zhang; Jing Zhu; Yunxiao Wang; Lingshuai Wang; Rui Liu; Liang Shi; Ang Ren; Mingwen Zhao (Environmental Microbiology, 2021)
Summary The cell wall integrity (CWI) signaling activates the transcription factor Swi6 through a MAPK signaling cascade in response to cell wall stresses. In this study, we observed two different mRNA variants of swi6 ( GlSwi6A and GlSwi6B ) existed, due to alternative splicing. Besides, the expression level of GlSwi6B was higher than that of the GlSwi6A mRNA variant. The co‐silencing of GlSwi6A and GlSwi6B was more sensitive to cell wall stress compared with WT, resulting in a decrease of 78% and 76% in chitin and β‐1,3‐ d ‐glucan content respectively. However, only the overexpression of GlSwi6B decreased the sensitivity to cell wall stress and increased the content of chitin and β‐1,3‐ d ‐glucan compared with the WT strain. Furthermore, Y1H, EMSA and BLI assays revealed that the GlSwi6B could bind to the promoters of chitin and glucan synthesis genes (GL24454 and GL18134). However, the binding phenome has not been observed in the isoform GlSwi6A. Taken together, our results found two different transcripts generated from Swi6 , in which the alternative splice isoform of GlSwi6B participates in regulating the CWI of G . lucidum . This study provides the first insight into the alternative splicing isoform of GlSwi6B in the regulation of CWI signaling in fungi.

The influence of partial pile cutting on the pile-anchor supporting system of deep foundation pit in loess area - Yunxin Zheng; Zhiping Hu; Xiang Ren; Rui Wang; Enxiang Zhang (Arabian Journal of Geosciences, 2021)

Unraveling Street-Level Air Pollution upon a Pivotal City of Yangtze River Delta, China - Rui Feng; Han Gao; Zhuo Wang; Kun Luo; Jian-ren Fan; Hui-jun Zheng (Aerosol Science and Engineering, 2021)

Invited review: human air-liquid-interface organotypic airway tissue models derived from primary tracheobronchial epithelial cells—overview and perspectives - Xuefei Cao; Jayme P. Coyle; Rui Xiong; Yiying Wang; Robert H. Heflich; Baiping Ren; William M. Gwinn; Patrick Hayden; Liying Rojanasakul (In Vitro Cellular & Developmental Biology - Animal, 2021)

α-Synuclein aggregation and transmission in Parkinson’s disease: a link to mitochondria and lysosome - Rui Wang; Hongyang Sun; Haigang Ren; Guanghui Wang (Science China Life Sciences, 2020)

Os4BGlu14, a monolignol β-Glucosidase, negatively affects seed longevity by influencing primary metabolism in rice - Rui-Juan Ren; Pei Wang; Li-Na Wang; Jing-Ping Su; Lin-Jing Sun; Yue Sun; De-Fu Chen; Xi-Wen Chen (Plant Molecular Biology, 2020)

Prevalence of Clonorchis sinensis infection in fish in South‐East Asia: A systematic review and meta‐analysis - Ying Zhang; Qing‐Long Gong; Qing‐Bo Lv; Yang‐Yuan Qiu; Yan‐Chun Wang; Hong‐Yu Qiu; Xin‐Rui Guo; Jun‐Feng Gao; Qiao‐Cheng Chang; Chun‐Ren Wang (Journal of Fish Diseases, 2020)
Clonorchis sinensis , an important fish‐borne zoonotic trematode, is widely distributed in South‐East Asia, especially in China. Infections from human and animal reservoir hosts occur due to the consumption of raw or undercooked fish with C. sinensis metacercariae. This study aimed to evaluate the prevalence of C. sinensis metacercariae in fish in South‐East Asia via systematic review and meta‐analysis. We searched PubMed, ScienceDirect, China National Knowledge Infrastructure, Wanfang and Chongqing VIP databases for studies published between 1976 and 2020 that are related to the prevalence of C. sinensis metacercariae in fish. Studies were screened with keywords based on inclusion and exclusion criteria. Seventy‐one eligible articles were identified, covering three countries: China, Korea and Vietnam. The pooled prevalence of C. sinensis metacercariae in fish from South‐East Asia was 30.5%, with 35.1% in China, 29.7% in Korea and 8.4% in Vietnam. In subgroup analyses of climate, season, water source and publication date, the highest prevalence was identified in the Dwb climate type (43.3%), summer (70.2%), river (34.5%) and pre‐2001 publications (38.9%), respectively. In comparison, the lowest prevalence was found in the Dfa climate type (14.5%), winter (19.5%), lake (8.0%) and post‐2001 publications (23.8%). Meta‐regression results indicated that country ( p = .009), the published time ( p = .035) and water source subgroups ( p = .003) may be the source of heterogeneity. Overall, our study indicates that a high prevalence of C. sinensis infections occurs in fish in China, Korea and Vietnam, illuminating a significant public health concern in these countries.

Electroacupuncture improves myocardial ischemia injury via activation of adenosine receptors - Yulan Ren; Zhihan Chen; Rui Wang; Yang Yu; Dehua Li; Yonggang He (Purinergic Signalling, 2020)
Electroacupuncture (EA) can improve myocardial ischemia (MI) injury; nevertheless, the mechanism is not entirely clear. And there were disagreements about whether the effect of EA at acupoint in disease-affected meridian is better than EA at acupoint in non-affected meridian and sham acupoint. Here, we showed that the effect of EA at Neiguan (PC6) is better than EA at Hegu (LI4) and sham acupoint in affecting RPP and ECG, increasing ATP and ADO production, decreasing AMP production, and upregulating the mRNA expression levels of A1AR, A2aAR, and A2bAR; knockdown of A1AR or A2bAR reversed the effect of EA at PC6 in alleviating MI injury; knockdown of A2aAR had no influence on the cardiac protection of EA at PC6; thus, the cardioprotective effect of EA at PC6 needs A1AR and A2bAR, instead of A2aAR; considering that the cardio protection of adenosine receptor needs activation of other adenosine receptors, one of the reasons may be that after silence of A1AR or A2bAR, EA at PC6 could not impact the expression levels of the other two adenosine receptors, and after silence of A2aAR, EA at PC6 could impact the expression levels of A1AR and A2bAR. These results suggested that EA at PC6 may be a potential and effective treatment for MI by activation of A1AR and A2bAR.

Role of the C9ORF72 Gene in the Pathogenesis of Amyotrophic Lateral Sclerosis and Frontotemporal Dementia - Zongbing Hao; Rui Wang; Haigang Ren; Guanghui Wang (Neuroscience Bulletin, 2020)

The study on loess liquefaction in China: a systematic review - Siyue He; Xiuling Wang; Haobo Fan; Hao Wang; Rui Ren; Chunxia Guo (Natural Hazards, 2020)

Technical efficiency estimation of China’s environmental protection enterprises and its heterogeneity - Ren Wang; Rui Wang; Xiaobo He (Environmental Science and Pollution Research, 2020)

Detection performance of azimuthal electromagnetic logging while drilling tool in anisotropic media - Zhen-Guan Wu; Lei Wang; Yi-Ren Fan; Shao-Gui Deng; Rui Huang; Tao Xing (Applied Geophysics, 2020)

Correction to: Description of Wenzhouxiangella salilacus sp. nov., a moderate halophilic bacterium isolated from a salt lake in Xinjiang Province, China - Shuai-Bo Han; Xin-Jun Hou; Yang-Huan Yu; Zhao Ju; Ran Zhang; Rui-Jun Wang; Yang-Hui Ye; Yan-Hu Ren; Wei-Yan Zhang; Min Wu (Antonie van Leeuwenhoek, 2020)

Poly-PR in C9ORF72-Related Amyotrophic Lateral Sclerosis/Frontotemporal Dementia Causes Neurotoxicity by Clathrin-Dependent Endocytosis - Rui Wang; Xingyun Xu; Zongbing Hao; Shun Zhang; Dan Wu; Hongyang Sun; Chenchen Mu; Haigang Ren; Guanghui Wang (Neuroscience Bulletin, 2019)

Changes in bacterial community structure and humic acid composition in response to enhanced extracellular electron transfer process in coastal sediment - Jiulong Zhao; Long Wang; Lili Tang; Rui Ren; Wuxin You; Robina Farooq; Zejie Wang; Yongyu Zhang (Archives of Microbiology, 2019)

Description of Wenzhouxiangella salilacus sp. nov., a moderate halophilic bacterium isolated from a salt lake in Xinjiang Province, China - Shuai-Bo Han; Xin-Jun Hou; Yang-Huan Yu; Zhao Ju; Ran Zhang; Rui-Jun Wang; Yang-Hui Ye; Yan-Hu Ren; Wei-Yan Zhang; Min Wu (Antonie van Leeuwenhoek, 2019)

Ethylene, xylene, toluene and hexane are major contributors of atmospheric ozone in Hangzhou, China, prior to the 2022 Asian Games - Rui Feng; Qing Wang; Cheng-chen Huang; Jin Liang; Kun Luo; Jian-ren Fan; Hui-jun Zheng (Environmental Chemistry Letters, 2019)

Comparative study on mitogenomes of green tide algae - Chuner Cai; Feng Liu; Ting Jiang; Lingke Wang; Rui Jia; Lingjie Zhou; Kai Gu; Jianfeng Ren; Peimin He (Genetica, 2018)

Alzheimer’s Disease Risk Variant rs2373115 Regulates GAB2 and NARS2 Expression in Human Brain Tissues - Guiyou Liu; Tao Wang; Rui Tian; Yang Hu; Zhifa Han; Pingping Wang; Wenyang Zhou; Peng Ren; Jian Zong; Shuilin Jin; Qinghua Jiang (Journal of Molecular Neuroscience, 2018)

Hi1a as a Novel Neuroprotective Agent for Ischemic Stroke by Inhibition of Acid-Sensing Ion Channel 1a - Yandong Ren; Chengchong Li; Jinlong Chang; Rui Wang; Yuhua Wang; Xiang-Ping Chu (Translational Stroke Research, 2018)

Spatial trends and pollution assessment for mercury in the surface soils of the Nansi Lake catchment, China - Ming-Yi Ren; Li-Yuan Yang; Long-Feng Wang; Xue-mei Han; Jie-Rui Dai; Xu-Gui Pang (Environmental Science and Pollution Research, 2018)

Photoperiodism dynamics during the domestication and improvement of soybean - Sheng-Rui Zhang; Huan Wang; Zhongyu Wang; Yao Ren; Lifang Niu; Jun Liu; Bin Liu (Science China Life Sciences, 2017)

Fine-mapping and identification of a novel locus Rsc15 underlying soybean resistance to Soybean mosaic virus - Ren Rui; Shichao Liu; Adhimoolam Karthikeyan; Tao Wang; Haopeng Niu; Jinlong Yin; Yunhua Yang; Liqun Wang; Qinghua Yang; Haijian Zhi; Kai Li (Theoretical and Applied Genetics, 2017)

Inoculation of Fe/Mn-oxidizing bacteria enhances Fe/Mn plaque formation and reduces Cd and As accumulation in Rice Plant tissues - Ming Fang Dong; Ren Wei Feng; Rui Gang Wang; Yang Sun; Yong Zhen Ding; Ying Ming Xu; Zhi Lian Fan; Jun Kang Guo (Plant and Soil, 2016)

Elevated IL-6 and TNF-α Levels in Cerebrospinal Fluid of Subarachnoid Hemorrhage Patients - Wei Wu; Yi Guan; Gang Zhao; Xi-Jia Fu; Tie-Zhu Guo; Yue-Ting Liu; Xin-Liang Ren; Wei Wang; Han-Rui Liu; Yun-Qian Li (Molecular Neurobiology, 2016)

Cryopreservation for retaining morphology, genetic integrity, and foreign genes in transgenic plants of Torenia fournieri - Jing-Wei Li; Hou-Hua Li; Ren-Rui Wang; Xiao-Xia Gao; Qiao-Chun Wang (Acta Physiologiae Plantarum, 2016)

Porcine epidemic diarrhea virus uses cell-surface heparan sulfate as an attachment factor - Chang-chao Huan; Yue Wang; Bo Ni; Rui Wang; Li Huang; Xiao-feng Ren; Guang-zhi Tong; Chan Ding; Hong-jie Fan; Xiang Mao (Archives of Virology, 2015)

Burkholderia metalliresistens sp. nov., a multiple metal-resistant and phosphate-solubilising species isolated from heavy metal-polluted soil in Southeast China - Jun Kang Guo; Yong Zhen Ding; Ren Wei Feng; Rui Gang Wang; Ying Ming Xu; Chun Chen; Xiu Li Wei; Wei Min Chen (Antonie van Leeuwenhoek, 2015)

A novel missense mutation in collagenous domain of EDA gene in a Chinese family with X-linked hypohidrotic ectodermal dysplasia - DAXU LI; RAN XU; FUMENG HUANG; BIYUAN WANG; YU TAO; ZIJIAN JIANG; HAIRUI LI; JIANFENG YAO; PENG XU; XIAOKANG WU; LE REN; RUI ZHANG; et al. (Journal of Genetics, 2015)

Expression Analysis of Two P450 Monooxygenase Genes of the Tobacco Cutworm Moth (Spodoptera litura) at Different Developmental Stages and in Response to Plant Allelochemicals - Rui-Long Wang; Jun Li; Christian Staehelin; Xiao-Wei Xin; Yi-Juan Su; Ren-Sen Zeng (Journal of Chemical Ecology, 2015)

Hyperacetylation of Histone H3K9 Involved in the Promotion of Abnormally High Transcription of the gdnf Gene in Glioma Cells - Zheng-Quan Yu; Bao-Le Zhang; Hai-Bo Ni; Ze-Hao Liu; Jian-Cun Wang; Qing-Xian Ren; Jian-Bing Mo; Ye Xiong; Rui-Qin Yao; Dian-Shuai Gao (Molecular Neurobiology, 2014)

Detection of respiratory syncytial virus fusion protein variants between 2009 and 2012 in China - Qiuling Xia; Lili Zhou; Caijing Peng; Rui Hao; Ke Ni; Na Zang; Luo Ren; Yu Deng; Xiaohong Xie; Linli He; Daiyin Tian; Lijia Wang; et al. (Archives of Virology, 2014)

Next generation sequencing-based molecular diagnosis of retinitis pigmentosa: identification of a novel genotype-phenotype correlation and clinical refinements - Feng Wang; Hui Wang; Han-Fang Tuan; Duy H. Nguyen; Vincent Sun; Vafa Keser; Sara J. Bowne; Lori S. Sullivan; Hongrong Luo; Ling Zhao; Xia Wang; Jacques E. Zaneveld; et al. (Human Genetics, 2014)

Niche Divergence Among Sex and Age Classes in Black-and-White Snub-nosed Monkeys (Rhinopithecus bieti) - Yi Wan; Rui-Chang Quan; Guo-Peng Ren; Lin Wang; Yong-Cheng Long; Xiao-Hu Liu; Jian-Guo Zhu (International Journal of Primatology, 2013)

Potato leafroll virus (PLRV) and Potato virus Y (PVY) influence vegetative growth, physiological metabolism, and microtuber production of in vitro-grown shoots of potato (Solanum tuberosum L.) - Jing-Wei Li; Biao Wang; Xiao-Ming Song; Ren-Rui Wang; Long Chen; Hao Zhang; Zhi-Bo Zhang; Qiao-Chun Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

CTLA-4 polymorphisms and systemic lupus erythematosus (SLE): a meta-analysis - Jin-Xia Zhai; Li-Wei Zou; Zhao-Xiang Zhang; Wen-Jing Fan; Han-Yong Wang; Ting Liu; Zheng Ren; Rui-Xue Dai; Dongqing Ye (Molecular Biology Reports, 2013)

Priming of Anti-Herbivore Defense in Tomato by Arbuscular Mycorrhizal Fungus and Involvement of the Jasmonate Pathway - Yuan Yuan Song; Mao Ye; Chuan You Li; Rui Long Wang; Xiao Chen Wei; Shi Ming Luo; Ren Sen Zeng (Journal of Chemical Ecology, 2013)

The effects of three years of fencing enclosure on soil seed banks and the relationship with above-ground vegetation of degraded alpine grasslands of the Tibetan plateau - Zhan-Huan Shang; Bin Deng; Lu-Ming Ding; Guo-Hua Ren; Guo-Sheng Xin; Zhi-Yun Liu; Yan-Long Wang; Rui-Jun Long (Plant and Soil, 2013)

Transcriptional control of human CD2AP expression: the role of Sp1 and Sp3 - Hua-Guo Xu; Wei Ren; Li Zou; Yi Wang; Rui Jin; Guo-Ping Zhou (Molecular Biology Reports, 2012)

Clinical Study of Autologous Cytokine-Induced Killer Cells for the Treatment of Elderly Patients with Diffuse Large B-Cell Lymphoma - Xue-chun Lu; Bo Yang; Rui-li Yu; Xiao-hua Chi; Shuai Tuo; Chao-wei Tuo; Hong-li Zhu; Yao Wang; Chao-guang Jiang; Xiao-bing Fu; Yang Yang; Yang Liu; et al. (Cell Biochemistry and Biophysics, 2012)

Induction of DIMBOA accumulation and systemic defense responses as a mechanism of enhanced resistance of mycorrhizal corn (Zea mays L.) to sheath blight - Yuan Yuan Song; Man Cao; Li Jun Xie; Xiao Ting Liang; Ren Sen Zeng; Yi Juan Su; Jing Hua Huang; Rui Long Wang; Shi Ming Luo (Mycorrhiza, 2011)

The characterization of two novel IRF-3 transcripts starting from intron 2 of the wild type of IRF-3 - Wei Ren; Hua-Guo Xu; Chao Lu; Rui Jin; Li Zou; Yi Wang; Guo-Ping Zhou (Molecular Biology Reports, 2011)

Direct repression of the human IRF-3 promoter by E2F1 - Hua-Guo Xu; Wei Ren; Li Zou; Yi Wang; Rui Jin; Guo-Ping Zhou (Immunogenetics, 2011)

Environmental controls over carbon exchange of three forest ecosystems in eastern China - GUI‐RUI YU; LEI‐MING ZHANG; XIAO‐MIN SUN; YU‐LING FU; XUE‐FA WEN; QIU‐FENG WANG; SHENG‐GONG LI; CHUAN‐YOU REN; XIA SONG; YUN‐FEN LIU; SHI‐JIE HAN; JUN‐HUA YAN (Global Change Biology, 2008)
Net ecosystem productivity (NEP) was continuously measured using the eddy covariance (EC) technique from 2003 to 2005 at three forest sites of ChinaFLUX. The forests include Changbaishan temperate mixed forest (CBS), Qianyanzhou subtropical coniferous plantation (QYZ), and Dinghushan subtropical evergreen broad‐leaved forest (DHS). They span wide ranges of temperature and precipitation and are influenced by the eastern Asian monsoon climate to varying extent. In this study, we estimated ecosystem respiration (RE) and gross ecosystem productivity (GEP). Comparison of ecosystem carbon exchange among the three forests shows that RE was mainly determined by temperature, with the forest at CBS exhibiting the highest temperature sensitivity among the three ecosystems. The RE was highly dependent on GEP across the three forests, and the ratio of RE to GEP decreased along the North–South Transect of Eastern China (NSTEC) (i.e. from the CBS to the DHS), with an average of 0.77 ± 0.06. Daily GEP was mainly influenced by temperature at CBS, whereas photosynthetic photon flux density was the dominant factor affecting the daily GEP at both QYZ and DHS. Temperature mainly determined the pattern of the interannual variations of ecosystem carbon exchange at CBS. However, water availability primarily controlled the interannual variations of ecosystem carbon exchange at QYZ. At DHS, NEP attained the highest values at the beginning of the dry seasons (autumn) rather than the rainy seasons (summer), probably because insufficient radiation and frequent fog during the rainy seasons hindered canopy photosynthesis. All the three forest ecosystems acted as a carbon sink from 2003 to 2005. The annual average values of NEP at CBS, QYZ, and DHS were 259 ± 19, 354 ± 34, and 434 ± 66 g C m −2 yr −1 , respectively. The slope of NEP that decreased with increasing latitude along the NSTEC was markedly different from that observed on the forest transect in the European continent. Long‐term flux measurements over more forest ecosystems along the NSTEC will further help verify such a difference between the European forest transect and the NSTEC and provide insights into the responses of ecosystem carbon exchange to climate change in China.

A novel drought-inducible gene, ATAF1, encodes a NAC family protein that negatively regulates the expression of stress-responsive genes in Arabidopsis - Ping-Li Lu; Nai-Zhi Chen; Rui An; Zhao Su; Bi-Shu Qi; Fei Ren; Jia Chen; Xue-Chen Wang (Plant Molecular Biology, 2006)

Transgenic Mice Can Express Mutant Human Coagulation Factor IX with Higher Level of Clotting Activity - Jing-Bin Yan; Shu Wang; Wen-Ying Huang; Yan-Ping Xiao; Zhao-Rui Ren; Shu-Zheng Huang; Yi-Tao Zeng (Biochemical Genetics, 2006)

Identification and functional characterization of a leucine-rich repeat receptor-like kinase gene that is involved in regulation of soybean leaf senescence - Xiao-Ping Li; Rui Gan; Peng-Li Li; Yuan-Yuan Ma; Li-Wen Zhang; Ren Zhang; Yong Wang; Ning Ning Wang (Plant Molecular Biology, 2006)

Safety analysis of water resources and eco-environment in Shiyang River Basin - Ji-shi Zhang; Yong-qiu Zhang; Rui-feng Pu; Ren-sheng Chen; Zhong-shan Cheng; Ming-quan Wang (Chinese Geographical Science, 2005)